Aluminum alloy and method for producing alloy
Through rapid solidification and plastic consolidation technology, the problem of instability of existing aluminum alloys at high temperatures is solved, and high strength and high ductility aluminum alloy materials are realized, which are suitable for high-temperature forming processes.
Patent Information
- Application Number
- CN202380038668.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-12
- Filing Date
- 2023-04-12
- Publication Date
- 2024-12-17
AI Technical Summary
The existing industrial forged aluminum alloys are produced through slow cooling processes, resulting in the formation of intermetallic phases and uneven structure, which limits the strength and ductility of the material, and the high-strength alloys are unstable at high temperatures and are difficult to effectively form.
Using rapid solidification process and plastic consolidation technology, aluminum alloys are quickly solidified through plastic deformation at high temperatures, and plastic consolidation at high temperatures to form fine crystal structures to improve strength and thermal stability, while controlling the chemical composition of the alloy to avoid primary birth The formation of intermetallic phases.
The high yield strength and good heat resistance of aluminum alloy are achieved, forming force is reduced, and mechanical properties are maintained at high temperatures, the growth of intermetallic phases and uneven structure are avoided, and the thermal stability and ductility of the material are improved.
Smart Images

Figure BDA0005119883810000161 
Figure BDA0005119883810000181 
Figure BDA0005119883810000182
Abstract
Description
[0001] The present invention relates to an aluminium alloy which is rapidly solidifying and plastically consolidated, in particular by plastic deformation under pressure at temperatures above 300°C. The aluminium alloy is more particularly a wrought aluminium alloy suitable for plastic deformation, in particular by hot forging (such as die forging). The invention also relates to a method for producing a rapidly solidifying, plastically consolidated aluminium alloy.
[0002] Current industrial forged aluminum alloys are not produced by a rapid solidification process, but by casting a molten alloy and solidifying it through a relatively slow cooling process. Industrial forged aluminum alloys are divided into several groups called series. They can be additionally grouped according to the type of the main mechanism that affects the strength of the alloy. The most popular constructional materials are defined as 6xxx, 2xxx and 7xxx series, and are precipitation strengthened. The 7xxx series is known to contain the strongest aluminum alloys, while the 6xxx series contains aluminum alloys of medium strength. For example, the yield strength (yield strength, YS) of 6082 alloy is about 350MPa, while the yield strength of 7075 alloy is about 500MPa. The main disadvantage of high-strength alloys is that the higher their strength, the more demanding the technology used to process the alloy, such as requiring high forming forces and complex heat treatment. In addition, corrosion resistance can be a problem, especially in high-strength 2xxx and 7xxx series.
[0003] Another group of wrought alloys includes the 3xxx and 5xxx series, where the primary strengthening mechanism is solid solution strengthening. These alloys are corrosion resistant, but their strength is significantly lower than that of the 6xxx series alloys. For example, the yield strength of 5083 alloy, one of the strongest alloys in the 5xxx series, is only about 200 MPa.
[0004] Most of these industrial alloys are mass-produced by slow cooling processes, which present several disadvantages. During the slow cooling process, alloying elements segregate within the dendrites and to the inter-dendritic region, and form intermetallic phases that grow during the cooling process. These phenomena severely constrain the field of standard industrial crystallization processes (using low cooling rates). In addition, the composition of industrial alloys is limited to a certain range.
[0005] Chemical segregation can create volumes (phases) in the material with a lower melting point. It can lead to incipient (localized) melting during hot forming, thus requiring lower forming temperatures. Industry is mitigating these effects to some extent by appropriate homogenization treatments at elevated temperatures.
[0006] Structural inhomogeneities and large, brittle intermetallic particles make the plastic forming process very difficult, if not impossible. The presence of intermetallic phases, which are usually large and rectangular or needle-shaped, can lead to the appearance of cracks inside the material that reduce its ductility. This problem arises especially when higher concentrations of alloying elements are applied: the chemical segregation becomes more pronounced, the intermetallic phases become larger, so much so that the casting process is no longer even possible. During slow crystallization, inhomogeneities can even lead to high concentrations of stress across the solidifying billet, which can cause the material to break during cooling.
[0007] The purpose of producing aluminum alloys by rapid solidification processes is to prevent the formation and growth of intermetallic phases during crystallization, as well as to reduce or inhibit the segregation of alloying components within the dendrites and inhibit segregation to the interdendritic region. Rapid solidification processes involve rapid / quick cooling of the liquid alloy, thus allowing the introduction of larger amounts of alloying elements without the negative effects mentioned above.
[0008] However, the cooling rate is physically limited by heat transfer phenomena and the heat capacity of the material. This means that it is necessary to limit the size of the material undergoing the cooling process. In fact, obtaining a uniform chemical composition requires very high cooling rates, which can only be obtained by producing fragments of the material. In practice, two main techniques are used: powder atomization and melt spinning. Both are characterized by a high surface area to volume ratio, which allows very fast extraction of heat. In particular, melt spinning is very effective in heat extraction by using an efficient heat transfer between the molten alloy and the surface of the cooling roller. As a result of these rapid solidification techniques, the crystalline material is produced in the form of a highly fragmented material, in particular with at least one dimension of less than 100 μm.
[0009] Rapidly solidified material must be consolidated to produce larger alloy pieces. This is typically achieved through a plastic consolidation process (such as through a hot extrusion process). In this process, the aluminum alloy is consolidated by plastic deformation under pressure at elevated temperatures. During the consolidation process, the particles (i.e., fragments) of the rapidly solidified alloy are subjected to both compressive and shear stresses. Individual rapidly solidified elements / particles must indeed be in very close contact to form new interatomic bonds. Plastic deformation is required to create new surfaces that are free of oxides and are therefore able to bond to each other. Due to the shear stress generated by the plastic deformation, the surface area to volume ratio of the particles increases, exposing new, oxide-free surfaces. At the same time, smaller grains are produced.
[0010] The main advantage of small grains is that the aluminum alloy becomes stronger. Grain boundaries are indeed obstacles to dislocation movement. The relationship between yield stress and grain size can be mathematically described by the Hall-Petch equation. Another advantage of small grains is that grain boundary sliding can be activated at higher temperatures, allowing the alloy to be formed with reduced stress / force at these higher temperatures.
[0011] However, a disadvantage of smaller grains is that the material has a higher amount of internal energy, which is stored in the form of a larger grain boundary surface area. This means that when such a material is heated, for example to improve its formability, the recovery mechanism becomes very active, leading to grain growth and loss of the positive characteristics of the alloy.
[0012] In practice, there are already some rapidly solidified aluminum alloys. Based on their applications, they can be divided into two groups. The first group includes high-strength alloys designed directly as replacements for 7xxx series alloys, while the second group includes aluminum alloys for high-temperature applications.
[0013] An example of an alloy belonging to the first high strength group is an alloy designed by Alcoa and presented in the article "Rapidly solidified aluminium alloys: market assessment", E. Lavernia et al., Journal of Metals, 1985. The alloys designated X7090 and X7091 are alternatives to the standard 7075 alloy. Depending on their composition and production route, the rapidly solidified alloys show a strength improvement of 10% to 15% over the commercial alloys. The observed improvement is minor, as precipitation strengthening remains the main strengthening mechanism controlling the mechanical properties, while the effect of grain refinement remains small.
[0014] A high strengthening effect is obtained by rapid solidification of a solid solution strengthened alloy. T. Tokarski et al. in the article “Microstructure and plasticity of hot deformed 5083aluminium alloy produced by rapid solidification and hot extrusion” in Archives of Metallurgy and Materials, Vol. 57, No. 4, 2012 (DOI: 10.2478 / v10172-012-0140-2) discloses a rapidly solidified and plastically consolidated fine grained aluminium alloy (fine grained aluminium alloy), which contains a combination of magnesium, manganese and a small amount of some transition elements. As described in the article, the 5083 series of aluminium alloys are produced both in the form of conventional alloys through a casting process and in the form of ultrafine grained alloys through a rapid solidification / plastic consolidation process. The exact composition of the alloy is not disclosed in the article, but the 5083 series aluminum alloy is described as containing 4.00-4.90 wt. % Mg, 0.40-1.00 wt. % Mn, maximum 0.40 wt. % Si, maximum 0.25 wt. % Zn, maximum 0.40 wt. % Fe, maximum 0.25 wt. % Cr and maximum 0.15 wt. % Ti.
[0015] The molten alloy composition is rapidly solidified by melt spinning in the form of strips with a thickness ranging from 50 to 100 μm. The rapidly solidified material is extruded at a temperature of 400°C with a cross section reduction area λ equal to 25. The same composition is also cast in a conventional manner, homogenized at 530°C for 12 hours, and then hot extruded in the same manner as the rapidly solidified material. Due to the fine grain structure, the rapidly solidified and extruded material has a higher yield strength than conventional casting alloys (i.e., a yield strength of 320 MPa), while the yield strength of conventional casting alloys is only 180 MPa, an increase of about 70%. Another advantage of the rapidly solidified material is that it has lower flow stress during hot deformation. Therefore, in other words, the rapidly solidified material is easier to form under hot conditions. At a constant strain rate of 10 -2 s -1 , and the maximum flow stress of the rapidly solidified material is 19 MPa at 450°C, while the maximum flow stress of the conventionally cast material is 48 MPa. The reduced flow stress is due to grain boundary sliding in the presence of a higher density grain boundary region, and therefore finer grains.
[0016] The strength of the rapidly solidified and extruded alloy is partly due to the solid solution strengthening effect of Mn, especially the solid solution strengthening effect of Mg in the aluminum matrix. However, grain refinement to an average grain size of 700nm is the main strengthening effect. Fine scale intermetallic phases with a size of up to 50nm and containing Mn, Fe and Cr are also formed. These particles are dispersed both inside the particles and along the grain boundaries. The particles present on the grain boundaries provide thermal stability to the alloy structure during hot deformation through so-called grain boundary pinning or Zener pinning. As presented in the article "The effect of solutes on grain boundary mobility during recrystallization and grain growth in some single-phase aluminium alloys" by Y. Huang, FJ Humphreys, Materials Chemistry and Physics 132 (2012) 166–174, additional grain growth inhibition factors can be related to the segregation of Mg to the grain boundaries.
[0017] Despite the thermal stabilization effect of dispersed nanoparticles and grain boundary element segregation, the rapidly solidified material lost about 10% of its hardness during the hot pressing test at 450°C, while the conventional cast material lost only about 1% of its hardness in this test. The initial hardness of the rapidly solidified and extruded alloy increased significantly from 111 Hv 0.5 (Vickers hardness) down to 98.5HV 0.5 The loss of alloy hardness is attributed to the coarsening of the grains or intermetallic phases. Due to the loss of alloy hardness, it is recommended to avoid alloy temperatures above 450°C.
[0018] As described in the article "Thermo-mechanical processing of rapidly solidified 5083aluminium alloy-structure and mechanical properties" by T. Tokarski et al. in Archives of Metallurgy and Materials, Vol. 60, No. 1, 2015 (DOI: 10.1515 / amm-2015-0028), the yield strength of the alloy described in the previous article can be improved by one-step and two-step thermomechanical treatments. The thermomechanical treatment consists of a cold rolling step followed by isothermal annealing at 300°C for 3 hours, and was repeated twice in further experiments, resulting in further refinement of the alloy's microstructure.
[0019] The increase in yield strength is due to the refinement of the alloy structure from an initial average grain size of 710 nm to an average grain size of 360 nm and 270 nm. The increase in yield strength conforms to the Hall-Petch relationship. The yield strength increases from 320 MPa for the as-extruded material to 373 MPa for one-step thermomechanical treatment and 419 MPa for two-step thermomechanical treatment. Even with such complex thermomechanical treatments, it is not possible to obtain high-strength aluminum alloys, especially with a yield strength of more than about 500 MPa. In addition, due to the thermomechanical treatment, the ductility / elongation of the material decreases from 20% to 12%. The thermal stability of the rapidly solidified material in the extruded state was also examined at a temperature of 500°C. After annealing at this temperature for 3 hours, the yield strength of the alloy decreased from 320 MPa to 130 MPa, and the average grain size increased significantly, i.e., from 710 nm to 100 μm. Despite the formation of highly dispersed intermetallic compounds, the rapidly solidified and extruded alloy is obviously not sufficiently stable to be exposed to temperatures above 450°C. Stronger alloys that have been thermomechanically treated have even lower thermal stability due to the increased internal energy resulting from the increased number of grain boundaries.
[0020] As described in the first article by T. Tokarski et al., it is known that the thermal stability of materials with an ultrafine grained structure can be improved by adding elements such as Zr, Sc, Cr and Mn, which form highly dispersed intermetallic compounds that provide thermal stability during hot deformation due to grain boundary pinning. In the tested alloys, the thermal stability is improved by the dispersoid formed by the Mn, Fe, Cr rich phases. However, the thermal stability of the aluminum alloy is still limited, which does not allow the alloy to be further deformed at elevated temperatures above 450°C. In addition, although the alloy is strengthened by the Hall-Page effect, its yield strength is still limited, i.e., about 320 MPa. Finally, even if the flow stress during hot deformation at high temperatures is reduced due to the grain boundary sliding effect, this flow stress is still high at the highest temperature of the alloy, i.e., at a temperature of 450°C and 10 -2 s -1 The strain rate is 19MPa.
[0021] Another method for strengthening rapidly solidified aluminum alloys such as AlMg4.5Mn (AA5083) is described in the manuscript " =A unique high strength AlMgSc type material concept processed by innovative technologies for aerospace applications" was disclosed in the paper published in World Powder Metallurgy Congress and Exhibition, World PM 2010. An aluminum alloy containing 3.6wt.% Mg, 1.4wt.% Sc, 0.2wt.% Zr and 0.3wt.% Mn was prepared. In order to be able to dissolve the alloying elements, the alloy must be heated to a temperature of 900°C. The alloy is heated under an argon atmosphere to prevent oxidation and the formation of hydrogen. In order to avoid the formation of intermetallic phases during rapid solidification, the molten alloy is rapidly solidified by melt spinning. The produced flakes are not subjected to a plastic consolidation process to produce a fine-grained structure. Instead, the rapidly solidified flakes are subjected to a heat treatment to produce nanoscale Al 3 (Sc 1-x ; Zr x ) precipitation in order to increase the strength of the alloy by precipitation hardening (hardness up to 240HV). The disadvantage is that high forming forces are still required. In addition, the high cost of scandium makes the alloy very expensive and therefore only suitable for high-end applications, especially aerospace applications.
[0022] Examples of rapidly solidified aluminum alloys belong to the second group, i.e., to the group of alloys that still maintain sufficient strength at higher temperatures, such as can be found in US10 232 442. The rapidly solidified aluminum alloy compositions disclosed in this US patent are suitable for applications where the alloy must maintain its mechanical properties at slightly higher temperatures, such as in the case of turbocharger compressor wheels. Although these alloys are dispersion strengthened, they are still unstable at higher temperatures, which is necessary to reduce the pressure of hot extrusion or hot forming of the alloy. In fact, in order to maintain the mechanical properties of the alloy, US10 232 442 teaches extruding rapidly solidified alloys under temperature-limited forming conditions below 275°C. The extruded alloy should also be subsequently formed at such a relatively low temperature, such as die forging. However, the disadvantage of such low temperatures is that the extrusion process and the subsequent forming process require relatively high pressure / force. Therefore, both the extrusion and forming steps require heavy and expensive tools and also involve high operating costs.
[0023] The alloy compositions disclosed in US 10 232 442 all contain a large amount of dispersoid forming elements. Although these alloys are suitable for use at relatively high temperatures, they still seem to be unstable at higher forming temperatures. Generally, all aluminum alloys designed for use under conditions of elevated temperatures are alloyed with a large amount of transition elements. Among these transition elements, Ni and Fe are used in the highest amounts as dispersoid forming elements because they can be easily alloyed into molten aluminum without significantly overheating the melt. However, even with a high content of these transition elements, a stable alloy cannot be obtained that can also be formed at high temperatures, for example to reduce flow stresses in a hot forging step.
[0024] Another example of a rapidly solidified aluminum alloy designed for use at relatively elevated temperatures is described in the article "Structural and mechanical features of rapidly solidified Al-2Fe-2Ni-5Mg alloy" by A. Kula et al., and in which not only a dispersion (colloid) is formed, but also Mg is used as a solid solution strengthening element in the aluminum alloy. Compared with the 5083 alloy presented in the article by Tokarski et al., it contains more alloying elements, namely, 2.73wt.% Fe and 2.37wt.% Ni in addition to 4.56wt.% Mg, which is mainly present in solid solution. Despite the presence of such a large amount of additional dispersion (colloid) forming alloying elements, the yield strength of the alloy at room temperature is only about 300Mpa. This yield strength is attributed to the solid solution hardening achieved by the addition of Mg and the dispersion strengthening achieved by the refinement of intermetallic compounds. It can be seen on the scanning transmission electron microscopy (STEM) image that the alloy does contain a large amount of dispersion (colloid), but these dispersion (colloid) bodies are quite large. In addition, the grain size of the alloy is also large, so that only limited Hall-Petch strengthening effects can be obtained. Not only is the mechanical strength of the alloy quite limited, but it is also obviously limited in its thermal stability. After deformation tests at increasing temperatures, the microhardness of the alloy drops significantly, especially after deformation at 450°C, where the microhardness drops by more than 30%.
[0025] US 4 726 843 discloses a rapidly solidified aluminum alloy which is described as having not only good high temperature strength but also high thermal stability combined with good ductility and toughness of the material. The alloy does not contain any Mg, and instead of Fe and Ni, it contains 2 to 5.5 wt.% Cr and 2 to 5.5 wt.% V as dispersed (colloid) forming alloying elements. The molten alloy is rapidly solidified at a very high cooling rate, and the rapidly solidified powder is subsequently consolidated by an extrusion process and subsequent heat treatment. A powder consisting of Al2O3 particles with a size of less than 0.1 μm is obtained. 13 Cr 2 and Al 10 The V intermetallic phase is a finely divided dispersion (colloid). In the example, the room temperature tensile strength of the extruded alloy obtained is 520 MPa. This extruded alloy has a relatively small ductility, i.e., only 10% of the limited elongation at break. During the subsequent heat treatment at 400°C for one or two hours, the Vickers hardness is significantly increased by precipitation hardening.
[0026] The binary phase diagrams of Al-Fe and Al-Ni show that the liquidus temperature of these alloys increases slightly with increasing Fe or Ni content. As mentioned above, it makes this type of alloy rich in chemical composition. The characteristics of the transition elements Cr and V presented in US 4 726 843 are opposite, characterized by a very steep rise in liquidus temperature as a function of element addition. Therefore, a high alloying temperature of 1150°C is required in US 4 726 843 to dissolve a large amount of alloying elements. At such high temperatures, it is necessary to apply under vacuum or inert gas conditions, making this alloy unsuitable for industrial production. The large number of relatively large dispersions (colloids) formed by high Cr and V additions does allow high strength to be obtained. However, these large dispersions (colloids) make the alloy more brittle, especially at higher temperatures. The force required to form the alloy also increases.
[0027] EP 0 577 944 B1 also discloses a rapidly solidified aluminum alloy, which contains a large amount of alloying elements, including elements such as V, Cr, Mn, Co, Mo, Nb, Ta, Mg, Cu and Zn, in addition to 5% to 10 atomic % of Ni. The aluminum alloy is produced by rapid solidification and subsequent extrusion processes at a temperature of 200 to 550° C. It has a fine-grained structure with an average grain size of 40 to 2000 nm, and it contains intermetallic compounds with an average grain size of 10 to 1000 nm. The obtained material has high tensile strength and high hardness. Due to the brittle nature of the alloy, the flow stress of the alloy is relatively high even at higher temperatures, making it necessary to use expensive heavy forging presses. In addition, due to the high nickel content, the thermal stability of the alloy is not good, making it impossible to increase the forming temperature. Another disadvantage of the presence of a large amount of Ni is that it reduces the corrosion resistance of the alloy. Finally, EP 0 577 944 B1 teaches that the amount of the matrix strengthening elements Mg, Cu and Zn should be kept below 4 atomic %, otherwise the strength of the alloy will decrease.
[0028] US 6 334 911 discloses an aluminum alloy comprising a combination of Cu with Cr and / or Mn, and optionally one or more transition elements V, Fe, Co and Ni. The alloy is rapidly solidified to obtain fine grains, and then heat treated or consolidated and compacted. In an example, the rapidly solidified aluminum alloy powder is extruded at a temperature of 320 to 500° C. At room temperature, the extruded material has a relatively high tensile strength ranging from 500 to about 700 MPa. The strength of these materials is due to solid solution strengthening, especially solid solution strengthening of Cu, and due to the formation of quasicrystals finely dispersed in the aluminum matrix, and the quasicrystals are formed due to the presence of Mn and / or Cr. In addition, when transition elements are present, these transition elements produce intermetallic compound phases, which are uniformly and finely dispersed in the alloy structure. An important disadvantage of this rapidly solidified alloy is the presence of copper, which negates the corrosion resistance of the alloy. In addition, iron and nickel also have a negative impact on corrosion resistance and the thermal stability of the alloy. Furthermore, in order to obtain high strength, Cr and some transition elements are used in relatively high amounts in the examples, resulting in alloys having relatively high liquidus temperatures requiring higher alloying temperatures.
[0029] WO 2015 / 169232 discloses an aluminum alloy which is not produced by a rapid solidification process but by a die casting process. The alloy is strengthened by solid solution strengthening and has 1 to 4 wt.% Mn to form Al 6 Mn phase, and has 0.1 to 5wt.% Mg. In addition, the alloy contains at least the rare earth element La to improve the metallurgical properties and fluidity of the aluminum alloy and ensure better anodizing performance. The alloy may also contain limited amounts of Co and Ti, acting as grain refining elements. Despite the presence of these alloying elements, the alloy compositions disclosed in the examples all have limited ultimate tensile strength (maximum value is 300MPa) and limited HV hardness (maximum hardness is HV 100). The yield strength of the alloy is not yet disclosed. In the example of WO2015 / 169232, the tensile strength of the alloy of formula Mn2.5Mg3La0.2 is only 275MPa, and the tensile strength can be increased to 300MPa by increasing the amount of Mg to 5wt.%. However, when the amount of Mg is further increased to 6wt.%, the tensile strength drops to 280MPa, so that the range of the amount of Mg is limited to 5wt.%.
[0030] The present invention relates to rapidly solidifying and plastically consolidating aluminum alloys which, when plastically consolidating, have much higher strength than these die casting alloys, in particular a yield strength at room temperature higher than 300 MPa or preferably even higher than 340 MPa. The object of the present invention is to provide an improved rapidly solidifying and plastically consolidating aluminum alloy which is preferably corrosion-resistant and allows combining a high yield strength at room temperature with good heat resistance and relatively low forming forces at high temperatures. Furthermore, in order to make the alloy easier to alloy and solidify, the liquidus temperature of the alloy should not be too high. The liquidus temperature of the alloy is preferably lower than 950° C., or more preferably even lower than 900° C.
[0031] The aluminum alloy according to the present invention is rapidly solidified and plastically consolidated, and comprises:
[0032] - between 3.00 wt.% and 10.00 wt.% magnesium (Mg);
[0033] - more than 1.00 wt.% but less than 6.00 wt.% manganese (Mn); and
[0034] - one or more transition elements, said transition elements being chosen from the group consisting of chromium (Cr), vanadium (V), titanium (Ti), zirconium (Zr), molybdenum (Mo), cobalt (Co) and niobium (Nb), said one or more transition elements having a total amount at least equal to 0.50 wt.%, and said maximum amount of transition elements being: 1.50 wt.% for Cr, 1.50 wt.% for V, 1.00 wt.% for Ti, 1.00 wt.% for Zr, 1.50 wt.% for Mo, 1.50 wt.% for Co and 1.00 wt.% for Nb.
[0035] Among them, aluminum alloys include:
[0036] - contains no or less than 2.00 wt.%, preferably less than 1.00 wt.% of zinc (Zn), no or less than 2.00 wt.%, preferably less than 1.00 wt.% of silicon (Si), no or less than 1.00 wt.% of scandium (Sc) and no or less than 1.00 wt.% of tungsten (W);
[0037] - does not contain other elements than Al, Mg, Mn, Cr, V, Ti, Zr, Mo, Co, Nb, Zn, Si, Sc and W, or the total amount of said other elements is less than 4.00 wt.%, preferably less than 2.00 wt.% and more preferably less than 1.00 wt.%; and
[0038] - Aluminum as balance.
[0039] In case the alloy includes Sc, the Sc content is preferably lower than 0.80 wt. % and more preferably lower than 0.60 wt. %.
[0040] The alloy according to the invention first solidifies rapidly. In this way, the formation of primary intermetallic particles (phases) is prevented or at least greatly reduced. The maximum amount of different alloying elements is also limited by the respective upper limits so that the required casting temperature is kept sufficiently low. The higher amounts of these transition elements, especially those elements different from Cr, do increase the liquidus temperature, making the alloying of the composition more difficult and less suitable for industrial processes. In addition, the higher amounts of transition elements, and especially Cr, can lead to the formation of brittle intermetallic phases, which can make the plastic forming process more difficult, if not impossible.
[0041] The rapidly solidified alloy is then subjected to plastic consolidation. During the plastic consolidation process, the particles (sheets) of the rapidly solidified alloy are subjected to both compressive and shear stresses. This is carried out at elevated temperatures, in particular at temperatures above 300° C. In this way, the alloy is consolidated and its grain structure is refined so that after plastic consolidation, the alloy has a fine-grained structure. By increasing the temperature during plastic consolidation, the formation of dislocations within the grains is avoided or at least reduced. In addition, secondary intermetallic particles, i.e., so-called dispersed (colloidal) bodies, are produced. The plastic consolidation process is preferably controlled so that these dispersed (colloidal) bodies are refined, i.e., so that they have a volume average size of preferably less than 50 nm.
[0042] As for the chemical composition, the alloy according to the present invention is first a solid solution strengthened by the amount of Mg contained in the aluminum matrix. In order to avoid the solidus temperature of the alloy being too low, this amount of magnesium is subject to an upper limit. The alloy is also an alloy strengthened by Mn solid solution. In contrast to Mg, Mn improves the strength of the alloy without reducing its solidus temperature. At 660°C, the solubility of Mn in Al is about 1.5wt.%, and at about 535°C it is still 0.5wt.%. At room temperature, the rapidly solidified alloy is therefore supersaturated with Mn. During the plastic consolidation process, Mn also contributes to the generation of dispersed (colloids) in the rapidly solidified alloy, i.e., small particles of intermetallic compounds containing Mn, Al and other alloying elements. The formation of small dispersed (colloids) is essential for stabilizing the fine-grained alloy structure by Zener pinning. In the amount of Mn present in the alloy according to the present invention, it is found to be very effective in forming alloy strengthening / stabilizing dispersed (colloids). In binary Al-Mn systems, these dispersions (colloids) can be formed especially by secondary Al2O3 formation at temperatures above 510 °C. 6 Mn, and especially by secondary Al formed below 510°C 12Mn formation, i.e., formation at the temperature at which plastic consolidation is performed. The coarse primary Al is avoided or at least significantly reduced by the rapid solidification process. 4 Mn and / or Al 6 The formation of Mn. When in the grains, especially Al 12 When the Mn intermetallic phase is formed, it can also provide a strengthening effect because it is semi-coherent with the surrounding aluminum matrix. The advantage of both Mg and Mn is that they can be easily dissolved in large quantities in the alloy composition, i.e., high alloying temperatures are not required. Even when more magnesium is added, the liquidus temperature of the alloy does decrease, and the liquidus temperature of the binary Al-Mn system containing 6 wt.% Mn is only about 720°C.
[0043] Compared to Ni and Fe, which are used in some prior art alloys to strengthen the alloy by forming a dispersion (colloid), Mn has a lower diffusion coefficient, making the dispersion (colloid) containing Mn more thermally stable. In addition, in the alloy according to the present invention, the dispersion (colloid) tends to form more at the grain boundaries rather than within the grains, especially during the plastic consolidation process. The alloy according to the present invention also includes one or more transition elements Cr, V, Ti, Zr, Mo, Co and Nb, whose diffusion coefficients are even lower than that of Mn. These transition elements can stabilize the dispersion (colloid) containing Mn by partially replacing Mn with one or more of these transition elements, especially Al. 12 Mn phase.
[0044] A relatively high total amount of transition elements is required in the alloy according to the present invention. The important discovery of the present invention is indeed that, by selecting transition elements and by their relatively large total amount, a large number of smaller dispersed (colloidal) bodies are produced, and the grain size of the plastically consolidated alloy can be reduced. The large number of small dispersed (colloidal) bodies produced by the presence of transition elements can thermally stabilize the fine-grained alloy structure, although the interface boundary energy caused by the increase in the number of grain boundaries (i.e., due to the finer grain structure) is higher. The fine-grained alloy structure provides a high yield strength through the Hall-Petch effect. In addition, the fine-grained alloy structure is obtained by a plastic consolidation process, which is preferably carried out at an elevated temperature so that no or less dislocations are produced in the grains, which will reduce the ductility of the alloy.
[0045] The alloy according to the invention has been found to have low flow stress or even superplastic behavior during hot deformation. Due to its high thermal stability, higher forming temperatures can be applied to even further reduce the flow stress. The low flow stress can be explained by the significant boundary sliding effect caused by the large number of grain boundaries, the small size of the dispersed (colloid) bodies and the fact that the dispersed (colloid) bodies are mainly present at the grain boundaries rather than within the grains.
[0046] The list of transition elements used in the alloy according to the present invention is selected from which only transition elements with low diffusion coefficients in aluminum are included. The use of such transition elements can produce smaller dispersions (colloids) and finer grains during plastic consolidation, and obtain alloys with good thermal stability. The quantity and price of the selected transition elements are also easily available, which allows the production of alloys on an industrial scale. The diffusion coefficients of the selected transition elements are much lower than those of Ni and Fe, and in contrast to, for example, Ni, Fe and Cu, they do not reduce the corrosion resistance of the alloy. Surprisingly, in combination with Mg and Mn, they can achieve high yield strength at room temperature, low flow stress during hot deformation, and ensure the preservation of a fine grain structure. They can also achieve slightly lower but still high yield strengths in the plastic consolidation state, in particular true yield strengths (YS, R) higher than 300MPa or even higher than 340MPa. 0.2 ) and high ductility, in particular an elongation at break of at least 15% or at least 18% or even higher at room temperature.
[0047] The amount of each transition element is limited by a maximum value. The maximum amount is determined by the solubility of the corresponding transition element in the aluminum alloy, and is also determined by the effect of the increase in the amount of the transition element on the yield strength and hot forming stress of the alloy. Chromium can be dissolved in a higher amount than the claimed maximum amount. However, it has been found that such a high amount of chromium will result in a more brittle alloy. Higher amounts of different transition elements do not always increase the yield strength of the alloy, but sometimes can even reduce its yield strength, for example, by forming a Mg-containing phase, thereby reducing the Mg concentration in the solid solution. In addition, higher amounts of alloying elements have a negative impact on the flow stress during hot deformation. The alloy according to the present invention must contain a minimum total amount of one or more transition elements in total, more specifically, a minimum total amount of at least 0.50wt.%, so as to be able to produce the minimum thermal stability of the alloy and the minimum amount of dispersion (colloid) required for the minimum mechanical properties.
[0048] As mentioned above, the aluminum alloy according to the present invention includes at least Mg, Mn and one or more transition elements selected from Cr, V, Ti, Zr, Mo, Co and Nb as alloying elements. Preferably, it does not contain other elements. However, other elements can be included in the alloy in a limited amount without negatively affecting its favorable properties. Specifically, Zn and Si can be present in a maximum amount of 2.0wt.%, while Sc and W can each be present in a maximum amount of 1.0wt.%. Zn can be used as a further solid solution strengthening element, but the strengthening effect is found to be minimal. In addition, it is found that adding more than 1.0wt.% of Zn will reduce the strength of the alloy, so it is preferred that the added Zn does not exceed 1.0wt.%. This effect of zinc can be attributed to the formation of various phases containing Mg and Zn, which deplete the solid solution of Mg. Sc is much more expensive than other transition elements. When used, in order to stabilize the intermetallic phase containing Al, Sc and Zr, it is preferably used in combination with Zr. Zn and Si are relatively inert, so they may be present in limited amounts up to 2.0 wt.%, especially when they are introduced into the alloy as impurities due to the use of secondary aluminum as a raw material.
[0049] In addition to the above elements, the alloy can still contain other elements / impurities, but in the same way as standard industrial alloys, the amount should be low enough, in particular the total amount is less than 4.0wt.%, preferably less than 2.0wt.% and more preferably less than 1.0wt.%. The main reason is that the corrosion resistance is low when they are present. Especially Cu, Fe, Ni, Bi, Sn and Pb reduce the corrosion resistance of the alloy. Considering the favorable effect on the mechanical properties of the alloy, the alloy can contain more Fe and Cu compared with other elements, although they have a negative impact on the corrosion resistance of the alloy. The alloy should preferably contain less than 3.00wt.% of Fe, preferably less than 2.00wt.% of Fe and more preferably less than 1.00wt.% of Fe and less than 2.00wt.% of Cu, and preferably less than 1.00wt.% of Cu. Other elements (i.e., Ni, Bi, Sn and Pb) should preferably not be present in the alloy or be present in an amount of at most 0.40wt.% or preferably at most 0.30wt.%. Furthermore, too high amounts of other alloying elements may have a negative impact on the mechanical properties of the alloy, since they may interfere with the solid solution strengthening effect of Mg and Mn and interfere with the combination of Mn with other transition elements to form fine intermetallic dispersions (colloids). Therefore, any other alloying elements should preferably not be present in the alloy, or the amount of each element should be up to at most 0.4 wt.%.
[0050] In an embodiment of the alloy according to the invention, the alloy comprises at most 1.20 wt. %, preferably at most 1.00 wt. % and more preferably at most 0.75 wt. % V.
[0051] The liquidus of the aluminum-vanadium phase diagram is very steep, so that reducing the vanadium content significantly reduces the liquidus temperature of the alloy. In addition, the inventors have discovered that the strength-enhancing effect of vanadium can be retained by replacing part of the vanadium with one or more other transition elements.
[0052] In an embodiment of the alloy according to the invention or according to the preceding embodiments, the alloy comprises at most 1.40 wt.%, preferably at most 1.30 wt.%, and more preferably at most 1.20 wt.% Cr.
[0053] Compared to vanadium, more chromium can be dissolved at a certain temperature, for example 750°C. However, the inventors have found that the maximum amount of chromium is preferably kept at a lower level, because a higher amount of chromium can make the alloy more brittle. In addition, the inventors have also found that the strength-increasing effect of chromium can be maintained by replacing part of the chromium with one or more other transition elements. In case the alloy should have high ductility, in particular high elongation at break, such as an elongation at break of at least 15 wt.%, then it is preferably chromium-free, or it should preferably contain at most 0.3 wt.%, preferably at most 0.2 wt.% chromium.
[0054] In an embodiment of the alloy according to the invention or according to any of the preceding embodiments, the alloy comprises at least 0.10 wt.%, preferably at least 0.20 wt.%, more preferably at least 0.30 wt.% and most preferably at least 0.40 wt.% Cr, and / or at least 0.10 wt.%, preferably at least 0.20 wt.%, more preferably at least 0.30 wt.% and most preferably at least 0.40 wt.% V. Preferably the alloy comprises both chromium and vanadium. It preferably comprises Cr and V in a total amount of at least 0.50 wt.%, preferably at least 0.70 wt.% and more preferably at least 0.90 wt.%.
[0055] Both chromium and vanadium, especially the combination of these two transition elements, have been found to be very effective in achieving the above advantages, such as ease of alloying, high tensile strength, thermal stability and hot formability. Only when the ductility of the alloy should be increased is the amount of chromium preferably limited.
[0056] In an embodiment of the alloy according to the invention or according to any of the preceding embodiments, the alloy comprises two or more, preferably three or more, of said transition elements.
[0057] The problem with transition elements is that they have a steep liquidus in the binary phase diagram containing aluminum, so that the temperature required for alloying the composition rises rapidly with increasing amounts of transition elements. In the alloys of the present invention, for transition elements in larger total amounts, higher liquidus temperatures can be avoided by using a combination of two or more transition elements. Indeed, it has been found that replacing one transition element with a combination of two or more transition elements can provide a higher total amount of transition elements in the alloy without increasing the liquidus temperature of the alloy, while still achieving the desired thermal stability and mechanical properties. In addition, when using the same amount of more different alloying elements, there is a synergistic effect on the yield strength of the alloy.
[0058] In an embodiment of the alloy according to the invention or according to any of the preceding embodiments, the alloy comprises Cr and / or V, preferably Cr and V, and additionally comprises at least 0.15 wt.%, preferably at least 0.20 wt.% Ti, at least 0.15 wt.%, preferably at least 0.20 wt.% Zr, at least 0.15 wt.%, preferably at least 0.20 wt.% Mo, at least 0.15 wt.%, preferably at least 0.20 wt.% Co and / or at least 0.15 wt.%, preferably at least 0.20 wt.% Nb.
[0059] The addition of these alloying elements can reduce the amount of Cr and / or V, so that the liquidus temperature of the alloy can be further reduced, or in other words, the temperature of the rapidly solidified melt can be further reduced. The negative effect of Cr on the brittleness of the alloy can also be avoided. In addition, when the same amount of one or more of these other transition elements is used to replace part of Cr and / or V, a synergistic effect of the yield strength of the alloy is observed.
[0060] In an embodiment of the alloy according to the invention or according to any of the preceding embodiments, the total amount of the one or more transition elements is greater than 0.70 wt.%, preferably greater than 0.80 wt.%, more preferably greater than 0.90 wt.% and most preferably greater than 1.00 wt.%.
[0061] The study found that, at least when the alloys were prepared by the same rapid solidification and plastic consolidation process, the higher the total amount of transition elements, the higher the yield strength and thermal stability of the alloy. Plastic consolidation at lower temperatures does give higher yield strengths, but lower thermal stability, while plastic consolidation at higher temperatures gives lower yield strengths, but higher thermal stability.
[0062] In an embodiment of the alloy according to the invention or according to any of the preceding embodiments, the total amount of the one or more transition elements is less than 3.00 wt.%, preferably less than 2.75 wt.%, more preferably less than 2.50 wt.% and most preferably less than 2.25 wt.%.
[0063] It has been found that higher amounts of transition elements have no or only relatively little improvement in yield strength / thermal stability. Higher amounts may even lead to the formation of brittle intermetallic phases, which can make the plastic forming process more difficult, if not impossible.
[0064] In an embodiment of the alloy according to the invention or according to any of the preceding embodiments, the alloy comprises at least 1.10 wt.%, preferably at least 1.20 wt.%, more preferably at least 1.30 wt.% and most preferably at least 1.40 wt.% Mn.
[0065] It has been found that this higher amount of Mn increases the yield strength of the alloy. Since a considerable portion of the Mn will remain in solid solution, the effect of increasing the amount of Mn on the formation of dispersed (colloidal) bodies is relatively large. These dispersed (colloidal) bodies are indeed formed only by the excess Mn in the supersaturated solid solution obtained after rapid solidification of the alloy. It has been found that Mn has a high strength-increasing effect.
[0066] In an embodiment of the alloy according to the invention or according to any of the preceding embodiments, the alloy comprises less than 5.00 wt. %, preferably less than 4.50 wt. % and more preferably less than 4.00 wt. % Mn.
[0067] Below these upper limits, significant increases in yield strength can be obtained by adding more Mn. However, higher amounts of Mn have been found to provide little or no increase in the strength of the alloy. In addition, higher amounts of Mn can lead to the formation of brittle intermetallic phases, which can make the plastic forming process more difficult, if not impossible.
[0068] In an embodiment of the alloy according to the invention or according to any of the preceding embodiments, the alloy comprises at least 4.00 wt.%, preferably at least 4.50 wt.%, more preferably at least 5.00 wt.%, most preferably at least 5.50 wt.% and even more preferably at least 6.00 wt.% Mg.
[0069] It was found that higher amounts of Mg increase the strength of the alloy. Increasing the amount of Mg has no or only a small effect on the flow stress and thermal stability during hot deformation. The solubility of Mg in aluminum is indeed very high, so that only at relatively low temperatures (i.e., at temperatures where the diffusion coefficient of Mg is also low) will the aluminum matrix become supersaturated with Mg.
[0070] In an embodiment of the alloy according to the invention or according to any of the preceding embodiments, the alloy comprises less than 9.00 wt. %, preferably less than 8.00 wt. % and more preferably less than 7.00 wt. % Mg.
[0071] The Mg content of the alloy is preferably below these upper limits, since the higher the Mg content, the lower the solidus temperature of the alloy. According to the binary Al-Mg phase diagram, the solidus temperature of an Al-Mg alloy containing 7 wt.% Mg is actually equal to about 550°C. This means that the alloy cannot be heated to higher temperatures, since otherwise it would begin to lose its structure and therefore its favorable mechanical properties. In addition, coarse primary brittle phases would be formed, which would reduce the ductility and strength of the alloy and make plastic forming (hot forging) difficult, if not impossible.
[0072] In an embodiment of the alloy according to the invention or according to any of the preceding embodiments, the plastically consolidated alloy and preferably even the hot-forged alloy has a true yield strength (YS, R) measured at 20° C. according to ASTM E8 / E8M-13a. 0.2 ) is at least 400 MPa, preferably at least 450 MPa, more preferably at least 500 MPa and most preferably at least 550 MPa.
[0073] Surprisingly, the alloy according to the present invention was found to be able to achieve such high true yield strength without dedicated thermomechanical treatments, which would induce dislocation and / or precipitation strengthening in the alloy, thereby reducing the ductility and hot formability of the alloy and would lead to more elaborate processing of the alloy (mechanical and / or precipitation strengthening by dedicated mechanical and / or thermal treatments).
[0074] In an embodiment of the alloy according to the invention or according to any of the preceding embodiments, the alloy, in particular as a plastically consolidated alloy, is subjected to a true strain rate of 10 -2 The maximum true stress in the compression test is less than 25 MPa, preferably less than 21 MPa and more preferably less than 18 MPa at 450°C, and / or less than 20 MPa, preferably less than 17 MPa and more preferably less than 14 MPa at 500°C, and / or less than 17 MPa, preferably less than 14 MPa and more preferably less than 8 MPa at 550°C.
[0075] Such low maximum true stresses at these temperatures enable the alloy to be hot forged with very low forming forces. The advantage is that smaller forming presses and smaller and less expensive tools can be used, and tool life is extended.
[0076] In an embodiment of the alloy according to the invention or according to any of the preceding embodiments, the alloy, in particular the consolidated alloy, has a true yield strength (Ys, R) measured at 20° C. according to ASTM E8 / E8M-13a. 0.2 ), and at 525°C at 10 -2 The maximum true stress in a compression test when the member is compressed to 50% of the initial height at a true strain rate is (expressed in MPa) less than 3.0%, preferably less than 2.0% and more preferably less than 1.5% of the true yield strength (expressed in MPa).
[0077] Surprisingly, the alloy according to the present invention was found to be able to achieve a high true yield strength and a maximum true stress during plastic deformation at 525°C, which is only a small fraction of the true yield strength of the alloy.
[0078] In an embodiment of the alloy according to the invention, the alloy comprises between 1.50 and 3.50 wt.%, preferably between 2.00 and 3.00 wt.%, Mn, and between 3.00 wt.% and 5.00 wt.%, preferably between 3.00 and 4.50 wt.%, Mg, the total amount of the one or more transition elements being less than 1.00 wt.%, and Cr being preferably absent or present in an amount of at most 0.3 wt.% or at most 0.2 wt.%. Preferably, the alloy has a percent elongation at break of at least 15%, preferably at least 18%, and a true yield strength (YS, R 0.2 ) is at least 320 MPa, preferably at least 340 MPa, both measured at 20°C according to ASTM E8 / E8M-13a. The true yield strength is more preferably defined by the following equation:
[0079] YS>525-10.el (Equation 1); or
[0080] More preferably defined by the following equation:
[0081] YS>530-10.el
[0082] Where -el is the percent elongation at break; and
[0083] -YS is the true yield strength in MPa.
[0084] The alloy according to the invention is able to combine high tensile strength with high elongation, thereby obtaining an alloy with tensile properties outside the area of existing standard wrought aluminium alloys. Figure 65 of the publication “Making sustainable aluminium by recycling scrap: The science of “dirty” alloys” by D. Raabe et al. in Progress in Material Science 128 (2022) shows the tensile properties covered by existing standard wrought aluminium alloys. The yield strength of these alloys can reach about 750 MPa, while the elongation can reach about 40%. However, non-standard wrought aluminium alloys combine a relatively high tensile strength of at least 320 MPa with an elongation of at least 15.
[0085] However, this combination of tensile properties is very interesting in applications such as automotive applications. For example, the body or other parts of a car must be hard / strong enough to provide the required intrusion resistance of the vehicle in the event of a collision, while at the same time they must be ductile to absorb the collision energy. Ductile standard alloys are less strong, so more material is needed to make the vehicle heavier and the collision energy higher. In practice, splices can be welded to the automotive parts to increase their hardness or strength, and partial softening can be applied to provide ductility. However, the alloys according to the present invention provide new possibilities to make different vehicle parts lighter, thereby also reducing the weight of the vehicle and the collision energy absorption.
[0086] In an embodiment of the alloy according to the invention or according to any of the preceding embodiments, the alloy has a liquidus temperature below 950° C., preferably below 900° C. and more preferably below 850° C. The liquidus temperature of the alloy is preferably above 600° C.
[0087] Such low liquidus temperatures can be achieved by limiting the amount of transition elements and / or by using combinations thereof. Lower liquidus temperatures are advantageous because lower temperatures are required to melt the alloy composition, and thus oxidation of the aluminum melt can also be more easily avoided, particularly in industrial production processes.
[0088] In an embodiment of the alloy according to the invention or according to any of the preceding embodiments, the alloy is plastically consolidated by plastic deformation under pressure at a temperature of at least 300° C. Preferably, the temperature at which the alloy has been consolidated is below the solidus temperature of the alloy, preferably at least 10° C. below said solidus temperature but above 350° C., preferably above 375° C. and more preferably above 400° C., said temperature preferably being between 400° C. and 550° C.
[0089] By solidifying the alloy at a temperature lower than its solidus temperature, the advantages of the rapidly solidified alloy structure can be maintained. Higher temperatures during plastic consolidation enhance the dynamic recrystallization of the alloy. Therefore, the formation of dislocations is avoided or further reduced, and the thermal stability of the alloy is enhanced. However, in most cases, when the alloy is consolidated at a higher temperature, a larger grain size will be obtained, and therefore the increase in strength is relatively small. Generally, a more solid alloy with higher (very high) yield strength can be obtained by plastically solidifying the alloy at a lower temperature. However, the thermal stability of this alloy is lower. In a preferred temperature range, high strength and thermal stability can be achieved, so that the alloy can be hot formed at a temperature that is easy to form the alloy, that is, significantly reducing the forging pressure.
[0090] In an embodiment of the alloy according to the present invention or according to any of the preceding embodiments, the alloy has an average grain size of plastic consolidation measured according to standard ASTM E2627-13 (2019) of less than 2000nm, preferably less than 1000nm, more preferably less than 800nm and most preferably less than 600nm.
[0091] The advantage of such fine-grained alloys is that their strength is increased due to the small grain size, i.e. due to the Hall-Petch effect. Furthermore, in the alloy according to the invention, it has also been found that the combination of a smaller grain size with a large amount of nanoscale dispersed (colloidal) bodies reduces the flow stress of the alloy during hot forming to very low values by activating grain boundary sliding processes within its grain boundary-rich network.
[0092] In an embodiment of the alloy according to the present invention or according to any of the preceding embodiments, the plastically consolidated alloy is additionally hot forged, in particular die forged, at high temperature and has an average grain size measured according to standard ASTM E2627-13 (2019) of less than 4000 nm, preferably less than 2000 nm, more preferably less than 1500 nm and most preferably less than 1200 nm.
[0093] The hot forging of the alloy is carried out at an elevated temperature in order to reduce the flow stress of the alloy and enable it to deform to a greater extent than at room temperature. During hot forging, the alloy has a temperature of more than 400°C, preferably more than 450°C, more preferably more than 475°C or most preferably even more than 500°C. It takes some time to fully and uniformly heat the solid alloy to such a high temperature and perform the forging step so that the alloy is subjected to a period of high temperature. Although the alloy is thermally stable, the larger grains of the alloy in particular will become coarser, thereby increasing the average grain size of the alloy. In this embodiment, due to the presence of multiple nano-dispersed (colloidal) bodies in the grain boundary region, the coarsening of the grains is limited, so that the final grain size still provides the required strength increase effect.
[0094] In an embodiment of the alloy according to the invention or according to any of the preceding embodiments, the alloy is substantially free of primary intermetallic phases, and preferably also free of dendrites.
[0095] This can be achieved by a rapid solidification process, in particular by rapidly solidifying the alloy from at least its liquidus temperature to its solidus temperature.
[0096] The invention also relates to a method for producing an aluminum alloy according to the invention. The alloy has a liquidus and a solidus temperature and a predetermined difference between the liquidus and solidus temperatures. Both temperatures are determined on an equilibrium phase diagram of the alloy.
[0097] In the first step, a molten aluminum alloy composition having the composition of the alloy according to the present invention is produced. The molten aluminum alloy composition is rapidly solidified in the form of a rapidly solidified material sheet, and the rapidly solidified material sheet is plastically consolidated to produce a plastically consolidated aluminum alloy.
[0098] By rapidly solidifying the molten alloy composition, the formation of primary phases (usually brittle phases) is avoided. The formation of dendrites is also avoided. All of these phases / structures have a negative impact on the strength and / or thermal stability of the alloy and the forces required during hot forging of the alloy. The rapid solidification of the alloy produces a more uniform phase and structure with a large amount of internal energy. During the subsequent plastic consolidation step, the rapidly solidified alloy sheet is not only consolidated, but also produces a fine-grained alloy structure and forms a dispersed (colloid) body that stabilizes the fine-grained alloy structure, especially at an energy level lower than the initial energy level of the rapidly solidified material.
[0099] After plastic consolidation, the alloy remains stable at a higher energy level. As a result, the alloy has increased strength. In addition, the grain boundary sliding process is more easily activated and more pronounced, thus providing lower hot forming forces.
[0100] In an embodiment of the method according to the invention, the rapidly solidified molten aluminum alloy composition has a liquidus temperature below 950° C., preferably below 900° C., more preferably below 850° C. and most preferably below 800° C. The liquidus temperature of the alloy is preferably above 600° C.
[0101] Therefore, aluminum alloys can be melted at relatively low temperatures, especially without the use of vacuum or inert gas, and oxidation of aluminum and the formation of hydrogen can be more easily avoided or reduced. In other words, due to such a low liquidus temperature, the alloy can be more easily produced on an industrial scale.
[0102] In an embodiment of the method according to the present invention or according to any of the preceding embodiments, a molten aluminum alloy composition is ejected from at least one nozzle for rapid solidification, the molten aluminum alloy composition leaving the at least one nozzle has a predetermined temperature once leaving the at least one nozzle, and is rapidly solidified by cooling to the solidus temperature of the aluminum alloy within a predetermined period of time at an average cooling rate, the average cooling rate being determined as the ratio of the difference between the predetermined temperature and the solidus temperature oversaid predetermined period of time, and the average cooling rate being higher than 10,000°C / sec and preferably higher than 100,000°C / sec.
[0103] When such a high cooling rate is applied, the molten aluminum alloy solidifies rapidly when ejected from the nozzle.
[0104] Preferably, the predetermined temperature is higher than the solidus temperature by at least 75% of the liquidus / solidus temperature difference, the predetermined temperature is preferably equal to or higher than the liquidus temperature, and more preferably at least 10°C higher than the liquidus temperature.
[0105] Only when the temperature of the molten aluminum alloy is below its liquidus temperature can the primary intermetallic phase and dendrites be formed. Therefore, in this embodiment, the formation of the primary intermetallic phase and dendrites can be minimized or even avoided.
[0106] In embodiments of the method according to the preceding embodiments, the molten aluminum alloy composition is supplied to the at least one nozzle through a conduit and is additionally heated in the conduit before being ejected from the nozzle, the conduit being preferably substantially completely filled with the aluminum alloy composition.
[0107] Aluminum oxidizes quite quickly already at relatively low temperatures when there is water vapor. In a furnace in which the aluminum alloy or its components are prepared and in which air is present, preferably only relatively low temperatures are applied to melt the aluminum alloy or its components. The temperature may be below the liquidus temperature, so that the aluminum alloy is not yet completely melted. Once the aluminum alloy enters the pipe leading to the nozzle, it is further heated to a higher temperature in the pipe so that the alloy is substantially completely melted before being ejected from the nozzle for rapid solidification. Since the pipe is substantially completely filled with the alloy composition, the aluminum will not oxidize once it enters the pipe, and can therefore be heated to higher temperatures without being oxidized. Therefore, in an industrial process, oxidation can be easily avoided without applying vacuum conditions or without operating under an inert atmosphere.
[0108] In an embodiment of the method according to the invention or according to the preceding embodiment, the rapidly solidifying material sheet is plastically consolidated by plastic deformation under pressure at a temperature of at least 300°C, preferably at least 400°C and more preferably at least 450°C.
[0109] During the plastic consolidation step, the rapidly solidified material sheet is subjected to compressive and shear stresses. The individual rapidly solidified sheets are brought into very close contact, enabling the formation of new interatomic bonds. Plastic deformation is required to produce new surfaces that are free of oxides and are therefore able to bond to each other. Due to the shear stress generated by the plastic deformation, the surface area to volume ratio of the particles increases, exposing new, oxide-free surfaces. At the same time, smaller particles are produced. During plastic consolidation, the temperature of the rapidly solidified material is preferably above 300°C. In this way, less force needs to be applied to the material. In addition, due to the higher temperatures during the plastic consolidation process that lead to dynamic recrystallization of the alloy, the formation of dislocations is avoided or at least significantly reduced, and the thermal stability of the alloy is enhanced.
[0110] In an embodiment of the method according to the invention or according to any of the preceding embodiments, the temperature at which the rapidly solidifying sheet of material is consolidated is below the solidus temperature of the alloy, preferably at least 10°C below the solidus temperature but above 350°C, preferably above 375°C and more preferably above 400°C, most preferably between 400°C and 550°C.
[0111] Such high plastic consolidation temperatures promote the effectiveness of consolidation. The flow stress of the alloy is lower at higher temperatures, which facilitates the deformation of the rapidly solidifying material sheet, which is required to achieve intimate contact. In addition, higher temperatures increase local diffusion processes, improving the effectiveness of inter-particle bonding.
[0112] In an embodiment of the method according to the present invention or according to the aforementioned embodiment, the rapidly solidified material sheet is consolidated by plastic deformation so as to reduce the average grain size of the consolidated aluminum alloy measured according to standard ASTM E2627-13 (2019) to a value less than 2000nm, preferably less than 1000nm, more preferably less than 800nm and most preferably less than 600nm.
[0113] The advantage of such a fine-grained alloy is that its strength is increased due to the small grain size (ie due to the Hall-Page effect). Furthermore, with the alloy composition according to the invention it has also been found that the smaller grain size reduces the flow stress of the alloy during hot forming by activating the grain boundary sliding process.
[0114] In an embodiment of the method according to the invention or according to any of the preceding embodiments, consolidation is performed by extruding a rapidly solidifying sheet of material with a cross section reduction λ of at least 3, preferably at least 6, more preferably at least 8 and most preferably at least 10.
[0115] For the consolidation process, not only compressive stresses are applied to the rapidly solidifying material sheet, but also shear stresses. The higher the cross-sectional reduction, the better the consolidation of the material. For lower values of cross-sectional reduction, good consolidation may require one or more additional plastic working steps, which can be provided in a subsequent hot forging step.
[0116] In an embodiment of the method according to the invention or according to any of the preceding embodiments, the consolidated aluminium alloy is hot forged, in particular die forged.
[0117] In some applications, the alloy according to the present invention can be plastically consolidated into a desired shape or close to a desired shape. In other applications, the shape of the part to be produced can be achieved or at least approached by hot forging the alloy, so that no or less machining is required to achieve the final shape. Therefore, the production process of the part requires less material, consumes less time and energy, and produces less material in the form of chips that need to be recycled.
[0118] Preferably, the consolidated aluminium alloy is hot forged at a temperature above 400°C, preferably above 450°C and more preferably above 475°C or above 500°C, but below the solidus temperature of the alloy, preferably at least 10°C below said solidus temperature.
[0119] The higher the forging temperature, the lower the pressure that needs to be applied to the material to forge the material. In the method according to the present invention, due to the thermal stability of the alloy, this higher forging temperature can be applied. In addition, the high thermal stability of the alloy allows the alloy to be processed in an isothermal forming scheme. This means that during plastic deformation (hot forging), the temperature of the entire workpiece remains substantially constant. Specifically, the temperature of the mold is maintained at or slightly below the temperature of the starting workpiece. This allows better temperature control and improved material flow, thereby enabling or closer to net shape forming (netshape forming) (no machining required).
[0120] Other advantages and characteristics of the present invention will become apparent from the following description of some specific embodiments of the aluminum alloy and the method for making the same according to the present invention. This description is given only as an example and is not intended to limit the scope of the present invention. The reference numerals used in the description refer to the accompanying drawings, in which:
[0121] Figure 1Schematically shows a possible embodiment of an apparatus for producing a molten aluminum alloy and for rapidly solidifying this alloy by means of a melt spinning device;
[0122] Figure 2 To illustrate the generation of coarse primary Al in the RS example 3 SEM image of the microstructure of Al-7 Mg-1V alloy with V intermetallic phase, where the alloy composition was rapidly solidified at a temperature of 650°C;
[0123] Figure 3 and Figure 4 and Figure 2 Similar, but showing the microstructure of the Al-7Mg-1V alloy solidified rapidly at 750°C and 850°C, and showing little or no coarse primary Al 3 V intermetallic phase;
[0124] Figures 5 to 7 is a magnified TEM image of an Al-7Mg-2Mn-1V-1Cr alloy plastically consolidated at 400°C; and
[0125] Figure 8 Grain orientation map obtained by TKD analysis of Al-7Mg-2Mn-1V-1Cr alloy plastically consolidated at 400°C.
[0126] The present invention generally relates to a novel aluminum alloy, in particular a cast aluminum alloy, that solidifies rapidly and plastically. Aluminum alloys have a liquidus and a solidus temperature. The liquidus temperature is the lowest temperature at which the alloy in equilibrium is completely liquid, while the solidus temperature is the highest temperature at which the alloy in equilibrium is completely solid. Both temperatures can be observed on the equilibrium phase diagram of the alloy. The microstructure and composition of the alloy according to the present invention can be combined with low thermal deformation stresses at room temperature to obtain a high yield strength, so that it can be easily formed by hot forging, in particular by hot die forging processes. High ductility combined with yield strength can also be obtained when the yield strength is still high, in particular above 300 MPa. The rapidly solidified and plastically consolidated alloy has a relatively high thermal stability, so that its yield strength is not lost or is lost only to a limited extent during the hot forging process. The liquidus temperature of the novel aluminum alloy can be kept low so that alloying and solidification of the alloy are easier, in particular on an industrial scale.
[0127] The alloy can be a monolithic material and can be used to produce aluminum parts. However, the alloy can also be included in a metal matrix composite (MMC) or a metal matrix nanocomposite (MMNC) material. A metal matrix composite is a composite material having at least two components, one of which is an aluminum alloy. The other material can be a different metal, or can be another material (such as a ceramic or an organic compound). MMCs are made by dispersing reinforcing materials into a metal matrix. For example, carbon fibers are commonly used in aluminum matrices. The matrix (i.e., aluminum alloy) is a monolithic material in which reinforcing steel is embedded and is completely continuous. MMNCs can be defined as a metal matrix composite reinforced by nano-reinforcements. The reinforcements in MMCs or MMNCs do not constitute part of the aluminum alloy forming the matrix. Therefore, when the aluminum alloy will be part of an MMC or MMNC, the composition of the aluminum alloy according to the present invention is given in weight percentage of the constituent alloying elements (excluding any reinforcements). In addition, the phase diagram defining the liquidus and solidus temperatures of the alloy is based only on the aluminum alloy forming the monolithic matrix material.
[0128] The alloy according to the present invention comprises aluminum and different alloying elements, including alloying elements providing solid solution strengthening and alloying elements intended to produce nano-scale dispersions (colloids) that contribute to obtaining and stabilizing a fine-grained alloy structure. The refined grain structure provides additional strengthening, making it possible to obtain high strength in combination with solid solution strengthening. In this way, neither cold working is required to increase the strength of the alloy, nor is any separate / dedicated precipitation hardening of the aluminum matrix within the grains by additional strengthening heat treatment operations. Cold working and separate precipitation hardening operations are preferably avoided or kept to a minimum, because both strengthening mechanisms have a negative impact on the plasticity / ductility of the alloy and bring additional workload (cost) to the production program.
[0129] Typically, the aluminum alloy according to the present invention includes between 3.00 and 10.00 wt.% Mg and between 1.00 and 6.00 wt.% Mn. For higher strength, it is preferred to include at least 4.00 wt.% Mg. If possible, for lower strength but higher ductility, include less Mg, in particular 3.00 wt.% or more, or 3.5 wt.% or more Mg. In addition, the alloy includes one or more transition elements selected from the group consisting of a maximum of 1.50 wt.% Cr, a maximum of 1.50 wt.% V, a maximum of 1.00 wt.% Ti, a maximum of 1.00 wt.% zirconium Zr, a maximum of 1.50 wt.% Mo, a maximum of 1.50 wt.% Co and a maximum of 1.00 wt.% Nb. The total amount of these transition elements is at least 0.50 wt.%. Other elements may be present in the alloy, but the alloy should not contain less than 2.00 wt.%, preferably less than 1.00 wt.% Zn, no or less than 2.00 wt.%, preferably no or less than 1.00 wt.% Si, no or less than 1.00 wt.% Sc and no or less than 1.00 wt.% W. Finally, the alloy should not contain other elements other than Al, Mg, Mn, Cr, V, Ti, Zr, Mo, Co, Nb, Zn, Si, Sc and W or the total content of these other elements should be less than 4.00 wt.%.
[0130] The aluminum alloy of the present invention is produced by preparing a molten aluminum alloy composition, by rapidly solidifying the molten aluminum alloy composition in the form of a rapidly solidified material sheet, and by plastic consolidating the rapidly solidified material sheet. Then, the plastically solidified alloy is preferably hot forged and optionally further machined to produce the desired parts.
[0131] Rapid solidification of the molten alloy composition is a mandatory step in the production of the alloy according to the present invention. The key factor is to prevent the growth of intermetallic phases during the crystallization of the molten alloy composition and the segregation of alloying elements to the dendrite area. In the alloy according to the present invention, these phenomena are avoided by increasing the crystallization rate through a rapid cooling process. The cooling rate that can be achieved is physically limited by heat transfer phenomena and the heat capacity of the material. The size of the material subjected to the cooling treatment must be limited. In fact, in order to achieve the desired chemical composition, very high cooling rates are required, which can be obtained by producing highly fragmented pieces of molten material. Two techniques can be used: powder atomization and melt spinning. Both are characterized by a high surface area to volume ratio, which can quickly extract heat. In particular, the melt spinning process achieves more effective heat extraction by utilizing an efficient heat transfer between the molten alloy composition and the surface of the cooling roller, preferably the surface of the copper roller. As a result of the rapid solidification technology, a solidified / crystallized material is produced in the form of a highly fragmented material, which is composed of sheets with at least one size less than 100um. Preferably, the pieces of solidified material have at least one dimension which is even smaller, in particular smaller than 80 μm or even smaller than 60 μm.
[0132] The expression "rapid solidification" means that during solidification, the aluminum alloy melt is heated at a speed of more than 10 000°C / sec (10 4 ℃ / sec), preferably higher than 100000℃ / sec (10 5 The average cooling rate is preferably higher than 10 000°C / sec (10 000°C / sec). In particular, the average cooling rate is calculated over the time interval from the moment when the accelerated extraction of heat from the liquid alloy composition begins until the average temperature of the alloy composition drops to its solidus temperature. The accelerated extraction of heat preferably starts from an average temperature of the alloy composition that is equal to or higher than the liquidus temperature of the alloy composition. The average cooling rate is preferably higher than 10 000°C / sec (10 000°C / sec) over the time interval between the moment when the alloy composition is at its liquidus temperature and the moment when the temperature of the alloy composition has dropped to its solidus temperature. 4 ℃ / sec) and more preferably higher than 100 000 ℃ / sec (10 5 ℃ / sec).
[0133] In practice, the molten aluminum alloy solidifies rapidly from the moment it is ejected from one or more nozzles. As described above, the molten aluminum alloy ejected from the nozzles can solidify in the form of a strip in a melt spinning process or in the form of a powder in a powder atomization process.
[0134] When the molten aluminum alloy leaves the nozzle or multiple nozzles, rapid solidification begins. At the outlet of the nozzle, the molten aluminum alloy has a substantially uniform predetermined temperature. If not uniform, the predetermined temperature is the volume-weighted average temperature of the molten aluminum alloy when it leaves the nozzle. The average cooling rate must be calculated over the interval in which the volume-weighted average temperature of the molten aluminum alloy drops from the predetermined temperature at the nozzle outlet to the solidus temperature of the aluminum alloy. The difference between these two temperatures divided by the time required to cool the molten aluminum alloy from the predetermined temperature to the solidus temperature is the average cooling rate, which must be higher than 10,000°C / sec (10 4 ℃) to carry out rapid solidification process.
[0135] The average cooling rate can be measured when suitable measuring equipment is available, but can also be calculated based on different parameters. The required cooling rate can also be determined by testing, starting with a cooling rate at which primary intermetallic phases are formed, and gradually increasing the cooling rate until a cooling rate is reached at which no primary intermetallic phases are formed during the rapid solidification step.
[0136] For a rapid solidification process by melt spinning, the average cooling rate can be calculated based on what is disclosed in the article "Analyses of the melt cooling rate in the melt-spinning process" by B. Karpe et al., Journal of Achievements in Materials and Manufacturing Engineering, Vol. 51, No. 2, April 2012. The contents of this article are incorporated herein by reference. In some of the figures of this article, an initial rapid drop in temperature from about 700° C. to 660° C. (i.e., to the solidus temperature of pure aluminum) can be observed, which applies to different strip thicknesses and different distances from the surface of the chill wheel. When this temperature drop is divided by the solidification time and these values are averaged to different distances from the surface of the chill wheel, the average cooling rate can be calculated.
[0137] For rapid solidification processes by gas (or liquid) atomization, the average cooling rate can be calculated based on calculations disclosed in the article "Rapidly Solidified Gas-Atomized Aluminum Alloys Compared with Conventionally Cast Counterparts: Implications for Cold Spray Materials Consolidation" by Bryer C. Sousa et al., Coatings 2020, 10, 1035. The contents of this article are incorporated herein by reference. The article gives a formula that can calculate the cooling rate. In the article Figure 3 It can be observed that the cooling rate depends particularly on the particle size of the atomized droplets. Other parameters are the specific heat of the metal droplets and the thermal conductivity of the gaseous species used during gas atomization.
[0138] Figure 1 Schematically shows an apparatus that can be used to produce a rapidly solidified aluminum alloy by a melt spinning process. The apparatus comprises a furnace 1 provided with a heater 2. Figure 1 As shown, the heater 2 may be an induction heater 2. However, other heaters are also possible, for example, a gas heater. The different elements of the aluminum alloy composition are introduced into the furnace, as pure elements or as a mixture (master alloy) to produce an aluminum alloy composition 3 in the furnace 1. Aluminum can be added as essentially pure aluminum, while other alloying elements are preferably added in the form of a master alloy (which also contains a portion of) aluminum.
[0139] The furnace 1 is connected to the nozzle 5 via a pipe 4 and can be opened via a valve ( Figure 1 The pipe 4 is closed (not shown). The pipe 4 comprises a pipe 6. The pipe 6 is provided with another heater 7, which is also an induction heater 7 arranged around the pipe 6. The pipe 6 has a widening portion, which forms a chamber 11 also heated by the heater 7. The aluminum alloy composition 3 is heated to a first temperature in the furnace 1 and is supplied to the inlet of the pipe 4 at this temperature. The furnace 1 and the pipe 4 are arranged vertically up and down so that the molten alloy composition 3 can flow from the furnace 1 to the nozzle 5 by gravity. The furnace 1 is closed by means of a cover 8 and by introducing a gas under pressure into the furnace 1, additional pressure can be applied to the molten composition 3. Alternatively, a pump (not shown) can be provided in the pipe 4. Preferably, the pipe 4 and the chamber 11 formed by the pipe 4 are completely filled with the molten alloy composition so that the molten composition flows through the pipe through the pipe flow. In this way, there is no or substantially no gas (e.g., air containing water vapor) in the pipe, so that the alloy composition does not undergo any oxidation process in the pipe 4.
[0140] The molten aluminum alloy ejected from the nozzle 5 reaches a rotatable cooling roller 9, which can be made of copper, copper-beryllium or stainless steel, for example. The roller 9 is internally cooled, for example by water, and rotates rapidly to achieve the desired rapid cooling rate. The liquid aluminum alloy solidifies in the form of a strip 10, or in the case where more nozzles 5 are arranged at the end of the pipe 4 (which can contain more than one or several parallel tubes 6), in the form of a plurality of strips. The strip thickness can be controlled by the rotation speed of the cooling roller 9, the ejection pressure, the nozzle slot size and the gap between the nozzle 5 and the roller 9. A higher cooling rate can be achieved by reducing the strip thickness, in particular to the above-mentioned preferred maximum size of 1.00, 0.80 or 0.60 μm. The strip can have a width of one to several millimeters, for example, a width between 1 and 10 mm, in particular a width between 1 and 5 mm.
[0141] In addition to using the cooling roller 9 to rapidly solidify the molten alloy, it is also possible to rapidly solidify by other existing methods, in particular by a spray forming process, in which the molten alloy is atomized in the form of droplets coming out of a nozzle to produce a powder. In order to further increase the cooling rate, the droplets are cooled in air or with a liquid such as water (in particular according to the granulation technology). The nozzle can also spray the molten alloy in water, in particular according to the known rotary water quenching technology.
[0142] Instead of producing the molten alloy composition in a furnace 1 , one or more further alloying elements may be injected into the pipe 4 , or into a mixing chamber arranged in the pipe 4 as part of the pipe 4 , and thus also preferably completely filled with the molten alloy composition.
[0143] An important advantage of the additional heating step by the additional heater 7 is that the aluminum alloy composition contained in the furnace 1 does not need to be completely melted, and in particular does not have to be heated to its liquidus temperature. When some alloying elements are injected into the pipe 4, the liquidus temperature of part of the alloy composition contained in the furnace 1 can also be reduced, optionally so that the part of the alloy composition can be heated to its (lower) liquidus temperature, while still avoiding or minimizing the oxidation of aluminum in the furnace. In this way, it is not necessary to apply a vacuum or an inert gas in the furnace 1. By the additional heating step in the pipe 4, in particular in the chamber 11 included therein, the entire alloy composition is then heated to a higher temperature, at which the entire alloy composition is completely or substantially completely melted before being ejected from the nozzle 5. The chamber 11 is intended to increase the residence time of the alloy in the pipe 4. The increased residence time enables any alloying elements that have not yet been completely melted / dissolved in the molten alloy to be further dissolved therein. Preferably, the molten aluminum alloy is heated in the pipe to a temperature equal to or higher than its liquidus temperature, preferably at least 10°C, or even 20°C higher than its liquidus temperature.
[0144] The molten aluminum alloy composition ejected from the nozzle 5 has a predetermined temperature once it leaves the nozzle, and is rapidly solidified by cooling to the solidus temperature of the aluminum alloy within a predetermined time period. For the rapid solidification process, the average cooling rate determined by the ratio of the predetermined temperature and the difference of the solidus temperature over the predetermined time period should be higher than 10000°C / sec (10 4 ℃ / sec), and preferably even higher than 100 000 ℃ / sec (10 5 ℃ / sec). A rapidly solidified aluminum alloy is an alloy that rapidly solidifies from a temperature of at least 75% of the difference between the liquidus and solidus temperatures of the aluminum alloy (higher than its solidus temperature). Therefore, when ejected from the nozzle, the molten aluminum alloy leaving the nozzle should therefore have such a high predetermined temperature. The predetermined temperature is preferably equal to or higher than the liquidus temperature of the alloy, and more preferably at least 10°C higher than the liquidus temperature. When the aluminum alloy is rapidly solidified at such a high temperature, the formation of a primary intermetallic phase can be avoided, so that the alloy is substantially free of a primary intermetallic phase, and preferably free of dendrites.
[0145] Since the rapidly solidified material is produced in the form of rapidly solidified material sheets, particularly strips 10, these rapidly solidified material sheets must be plastically consolidated in the next step to produce a solid sheet of alloy that can be further processed into a final product by hot forging and / or machining. When produced in the form of strips, the rapidly solidified material sheet can first be cut into smaller pieces. In this way, the particles / sheets of the rapidly solidified material can be more easily compacted to remove the gaps / voids between the particles.
[0146] Plastic consolidation is the necessary step of converting the broken rapid solidification material into a useful solidified block form (that is, converted into a solid sheet of alloy material). In order to achieve this, the individual sheets (particles) of the solidified material must be put together in a very close contact mode so that new interatomic bonds are formed. However, very close contact is not enough because aluminum and its alloys form a continuous and tight oxide layer (this is generally referred to as aluminum passivation) on its surface. In other words, due to these oxidation processes, no new metal surface can be used for correct combination. Therefore, the second requirement that must be met during plastic consolidation is to create an oxide free surface portion on the particles. During the plastic consolidation step, the isolated particles are preferably compressed together in a closed space and are subjected to the force that forces them to change their initial shape. By doing so, the above two requirements are met simultaneously. From a physical point of view, the feature of the plastic consolidation process is the stress component with a large hydrostatic component that presses the particles tightly together and the shear component that deforms the particles. When the particles are pressed together, they will be deformed to a certain extent to remove the gap between the particles. However, due to shear stresses, the surface area to volume ratio of the particles always increases, thus creating / exposing new oxide free surface portions.
[0147] The simplest way to obtain the required combination of pressure and shear stress on an industrial scale is through an extrusion process. Preferably, a sheet of rapidly solidifying material is first compacted to form a billet, which is preheated and then extruded through a die opening. An important parameter of the extrusion process is the cross-sectional reduction λ, which is the ratio between the cross-sectional area of the billet and the cross-sectional area of the extrusion leaving the die opening. The cross-sectional reduction area is preferably at least equal to 10. However, smaller cross-sectional reduction areas may also be used, particularly in cases where the extruded aluminum alloy is subsequently hot forged, particularly in the case of die forging. During such a hot deformation step, the produced parts are indeed further plastically consolidated. In addition, the extrusion process can be followed by one or more further plastic consolidation processes.
[0148] Instead of or in addition to the extrusion process, other consolidation techniques that can be applied, such as multi-step forging, ECAP (Equal Channel Angular Pressing) or any other technique characterized by the above-mentioned tensors can be used for plastic consolidation purposes. In particular, ECAP can be used after the extrusion process, in particular when the extrusion process is carried out with a smaller cross-sectional reduction. The ECAP process can be carried out directly on the extruded parts, so they are still hot. During the ECAP process, the material is pressed through a die consisting of two intersecting channels with the same cross-section. The advantage of the ECAP process is that the cross-section of the component does not change, in particular does not decrease. In the ECAP process, the component undergoes severe plastic deformation, which not only helps to refine the grains, but also helps to additionally break and refine the oxide layer between the aluminum parts / particles. More than one ECAP step can be performed in succession.
[0149] Before the rapidly solidified material is subjected to the plastic consolidation step, it is heated to a predetermined temperature, i.e., the temperature at which the plastic consolidation process is performed. The indicated temperature is the volume-weighted average temperature of the rapidly solidified material, in particular the volume-weighted average temperature of the billet of the rapidly solidified material, which is being plastically consolidated, in particular extruded. Higher plastic consolidation temperatures improve the consolidation effectiveness. The alloy flow stress is lower at higher temperatures, which is conducive to the deformation of the initial particles (rapidly solidified material sheets) to achieve close contact and produce new oxide free surface parts. Additionally, higher temperatures increase the local diffusion process and improve the effectiveness of inter-particle bonding. The extreme upper limit of the consolidation temperature is related to the solidus temperature of the alloy. For the alloy according to the present invention, the magnesium content controls the lowest melting point (solidus temperature) of the alloy, i.e., the temperature at which the alloy begins to melt when heated. During all processing steps after rapid solidification, the material must be in a solid state. Any local melting will lead to the formation of a near-equilibrium structure, characterized by chemical segregation and the formation of larger intermetallic phases. In the case of the alloy according to the present invention, magnesium controls the lowest value of the melting temperature range. In particular, the melting point (solidus temperature) of alloys with magnesium concentrations between 4 and 7 wt.% is in the range of about 550°C to about 590°C, depending on the magnesium concentration, and decreases as the magnesium concentration increases. The diffusion process imposes additional constraints on the plastic consolidation temperature. Higher temperatures mean more intense diffusion and faster alloy structure coarsening. The preferred temperature processing window for plastic consolidation is between 400°C and 500°C. In this preferred temperature range, the flow stress is small enough for effective plastic consolidation in a typical industrial press, and the diffusion is not too severe to destroy the highly fine dispersed (colloidal) microstructure of the alloy.
[0150] As a result of plastic consolidation, a highly refined microstructure of the consolidated material is achieved. Different structural optimization processes are carried out simultaneously. The deformation applied by external forces is generating a large number of dislocations, which are the driving force of the recrystallization process. This is called dynamic recrystallization. The final state of the microstructure depends on the intensity of these processes: the applied deformation tends to reduce the grain size, while higher temperatures tend to increase the grain size. However, the alloy composition according to the present invention can shift the balance to smaller grains through the thermal stability of the alloy structure. In the alloy according to the present invention, small intermetallic phases / dispersed (colloids) are indeed produced as grain boundary stabilizing elements. The more nanoscale phases there are in the microstructure, the better the pinning effect that can be achieved. These phases / dispersed (colloids) are also formed in situ during the plastic consolidation process. The aluminum matrix is supersaturated in the alloying components, and as long as the appropriate conditions (high temperature and diffusion path) are given, a dispersed (colloid) body will be formed. The low diffusion coefficient of the alloying elements greatly limits the growth of the dispersed (colloid). Therefore, the final grain size depends on the processing conditions and the number and size of the dispersed (colloid). With the alloy composition according to the invention, a grain size in the range of 500 nm can be easily obtained. This small grain size significantly contributes to the mechanical strength of the alloy in the cold state. In addition, low flow stresses can be obtained at higher temperatures (i.e., during hot forging).
[0151] The plastic consolidation process can directly form the final composition, particularly in the form of extruded profiles. However, an additional hot forging / forming step will usually be adopted. During hot forming, the same temperature constraints as during the plastic consolidation process are applied. The same mechanism is applicable to dynamically rebuild microstructure (dynamic recrystallization) during the deformation process. However, alloy according to the present invention can apply higher temperature during the forming step, so that the forming step is easier. Although some strength will be lost when applying higher forming temperatures, the initial strength of the plastic solidified alloy can be high enough to allow the use of this higher forming temperature. By the coarsening of the alloy structure, the thermal stability of the final component is improved to a certain extent.
[0152] The fine grain structure of the plastic solidified alloy allows the activation of the grain boundary sliding process during the next hot deformation step. Positive aspects include smaller forming presses, smaller and cheaper dies, and extended die life. Finer grain structures can also obtain ductile alloys that still have high strength. The ductility of the alloy can especially be improved by reducing the amount of Mg and selectively increasing the amount of Mn. In addition, finely dispersed alloying elements provide higher thermal stability to allow processing under isothermal forming schemes. This means that during plastic deformation, the temperature can remain almost constant. In this way, the temperature can be better controlled, and improved material flow can be achieved, so near net shape forming is achieved.
[0153] During forming after plastic consolidation, the microstructure of the alloy will generally coarsen to some extent. During hot deformation, the diffusion process is strengthened (there are more active diffusion paths, especially dislocation nuclei and new grain boundaries), resulting in dispersed (colloid) bodies and grain coarsening. The final effect depends on the processing conditions. After plastic consolidation, the average grain size of the alloy is preferably less than 2000nm, preferably less than 1000nm, more preferably less than 800nm and most preferably less than 600nm. Combined with the small size of the dispersed (colloid), such a fine-grained structure can activate grain boundary sliding during hot deformation. After the hot forging step, the average grain size of the alloy is preferably still less than 4000nm, preferably less than 2000nm, more preferably less than 1500nm and most preferably less than 1200nm. After the hot forging step, the small grain size is particularly important for improving the mechanical strength of the alloy.
[0154] The strength of the alloy according to the present invention is directly related to two strengthening mechanisms, i.e., solid solution strengthening and grain size strengthening (following the Hall-Petch rule). When a grain size of the order of 500nm is produced, the alloy according to the present invention can easily obtain a yield strength higher than 600MPa. Since the alloy is produced under hot conditions, the dislocation density is low, and the plasticity of the alloy will not deteriorate. For lower yield strength, higher ductility can also be obtained. This is contrary to the cold forming / processing step, during which the dislocation density increases, resulting in material strengthening, but at the same time losing plasticity. In addition, the dispersion (colloid) produced during the plastic consolidation process is preferably produced at the grain boundary to stabilize the fine grain structure and allow the grain boundary to slide. Therefore, avoid or at least minimize the precipitation hardening of the aluminum matrix. This is advantageous because the precipitation strengthening of the alloy has a negative impact on the flow stress of the alloy during hot deformation, and the grain size strengthening of the alloy reduces the thermal flow stress of the alloy, and can make the alloy have uniform superplastic properties. A dedicated precipitation hardening step can be applied, but these steps are preferably omitted. Additional benefits arise from the lack of precipitation strengthening procedures, which are usually performed in standard alloys and require additional heat treatment steps, increasing the cost of the product through additional time, infrastructure and energy usage. In addition, alloys with higher ductility can be obtained.
[0155] The following examples illustrate some embodiments of the alloys of the present invention, methods of making the same, and some of the advantageous properties that the alloys according to the present invention can provide.
[0156] Examples of alloying and rapid solidification techniques
[0157] The ternary alloy composition consists of aluminum, 7 wt.% magnesium and 1 wt.% vanadium. The alloy composition is Figure 1 The device shown schematically is fabricated and rapidly solidified.
[0158] Based on the binary Al-V phase diagram, the solidus temperature of the alloy in the absence of magnesium is about 820°C. Aluminum, magnesium and vanadium are placed in a furnace 1 and heated therein to a temperature of 650°C. This temperature is lower than the solidus temperature of pure aluminum (660°C), but the solidus temperature of the aluminum / magnesium solid solution is much lower (only about 550°C). The alloy composition is only partially molten and, based on the phase diagram, contains a certain amount of undissolved Al 3 V intermetallic phase.
[0159] The partially molten alloy composition is further heated in the chamber 11 by another heater 7 and then rapidly solidified by melt spinning on a water-cooled copper cooling roller 9. The thickness of the produced strip 10 is about 50 μm and the width is about 3 mm. The residence time of the alloy in the chamber 11 is equal to about 30 s.
[0160] Figure 2 FIG. 4 shows the microstructure of the rapidly solidified alloy composition without additional heating by the heater 7. A large number of primary Al2O3 particles with a maximum diameter of not more than 20 μm can be observed. 3 V intermetallic phase.
[0161] Figure 3 and Figure 4 The microstructures of the rapidly solidified alloy composition heated to 750°C and 850°C by heater 7 are shown. Figure 3 In the structure of Al 3 The V intermetallic phase forms far fewer particles (only one), while Figure 4 In the alloy, there are no longer any intermetallic particles larger than 1 μm. In fact, the alloy is heated to a temperature above its liquidus temperature, so that the molten alloy does not contain any primary intermetallic phase. In addition, the alloy is solidified so quickly that during the crystallization phase (i.e., when cooling from its liquidus temperature to its solidus temperature), no primary intermetallic phase can be formed.
[0162] In the final experiment, the distance between the location where the liquid alloy composition was applied to the roller 9 and the solidification front was determined by a camera. It took about 0.00025 seconds for the alloy to reach the solidification front. During this time, the temperature of the alloy composition on the roller 9 dropped from about 850°C to about 550°C, so the average cooling rate was estimated to be about 1 200 000°C / s.
[0163] Examples of Alloy Compositions and Mechanical Properties
[0164] A number of different alloys according to the invention and a number of comparative alloys have been prepared. The composition and mechanical strength of the alloys are shown in Table 1.
[0165] Table 1a and b:Composition (wt.%) and mechanical strength (HV: Vickers hardness, YS, R 0.2 : True yield strength, in MPa), including alloys according to the present invention and comparative alloys.
[0166]
[0167] Alloys Nos. 20 and 21 can also be produced by replacing all or part of the Co with similar amounts of Mo or Nb. This results in alloys with hardness and yield strength similar to those of alloys Nos. 20 and 21.
[0168] All components are given in weight percentage, aluminum is balanced to 100%. The "Total" row represents the total amount of disperse (colloid) body forming elements, that is, the total amount of all elements other than Al, Mg and Mn. The alloy prepared with the composition shown was heated to above its liquidus temperature and rapidly solidified by casting on copper rolls and then extruded at a temperature of 400°C with an area reduction ratio of 16. The composition was changed to show the effect of the solid solution strengthening elements and the disperse (colloid) body forming elements on the mechanical properties represented by the material hardness (determined by compression) and yield strength (measured by elongation test).
[0169] First, the yield strength of the different alloys was found to be linearly related to the hardness values, more specifically according to the following equation:
[0170] YS=4.0876HV-175.65,
[0171] Among them, R 2 Equal to 0.98.
[0172] Therefore, the Vickers hardness value is a good indicator of the tensile strength of the alloy.
[0173] Table 1 shows that the highest strength is obtained by adding both solid solution strengthening elements and dispersion forming elements. The data in the table allow the analysis of the influence of specific elements on the mechanical properties of the material.
[0174] For example, keeping the amount of other elements unchanged, increasing the Mg content by 5wt.%, 6wt.%, and 7wt.% (see alloys No. 4, 6, and 11) results in hardness values of 184HV, 192HV, and 200HV, respectively. Therefore, the increase in Mg content has a clear advantage in terms of material strength. Equally important, it has also been found that increasing the Mg content can prevent grain growth during the hot forming process, resulting in the formation of a smaller grain size.
[0175] Similar effects can be observed for increasing Mn content. For example, adding 2wt.% Mn to an alloy containing 7wt.% Mg and 1wt.% V increases the hardness from 132HV to 183HV (see alloys No. 8 and 10), while increasing the Mn content from 2 to 3.5wt.%, increases the hardness from 200HV to 223HV (see alloys No. 11 and 18). In addition to the solid solution strengthening effect, Mn also produces small dispersions (colloids), resulting in an additional increase in strength.
[0176] Not all elements have a positive effect on solid solution strengthening. Comparing alloys 4 and 5, it can be seen that the addition of large amounts of Zn has a negative effect on the final mechanical properties. This effect can be attributed to the formation of various phases containing Mg and Zn, which in other alloys can provide solid solution strengthening and precipitation hardening of the alloy, but in the alloy according to the present invention, they effectively deplete the Mg content in solid solution. Other elements that are commonly added to aluminum alloys (such as, for example, copper) were not tested because they have a negative impact on the corrosion resistance of the alloy.
[0177] A similar analysis can be performed for the dispersion (colloid) forming elements. It is clear that an increase in their concentration leads to a significant increase in hardness. Based on data from different alloys (Alloys No. 10-17 and No. 19-21) containing 7 wt.% Mg and 2 wt.% Mn, the following linear relationship was found between the "sum" of the different dispersion (colloid) forming elements (V, Cr, Zr, Ti and Co) and the hardness of the alloy:
[0178] HV=13.965sum+171.53,
[0179] Among them, R 2 Equal to 0.89.
[0180] Based on this relationship, a minimum of 0.5 wt. % of the transition element in dispersion (colloid) formation will be able to achieve a hardness of about 180 HV, or a corresponding yield strength of about 560 MPa.
[0181] The influence on the hardness value (and therefore also on the tensile strength of the alloy) depends not only on the amount of dispersed (colloidal) forming elements, but also on the elements themselves and their specific combination (this is why the R of the linear equation is 2 For example, in alloys No. 2 and 3, and No. 8 and 9, the strengthening effect of Cr appears to be slightly higher than that of V.
[0182] It is important to emphasize that the dispersed (colloid) forming elements not only have an effect on the strength of the alloy, but they also provide the desired grain stabilization effect. It is also an important discovery that several dispersed (colloid) forming elements can be used simultaneously, each element in a smaller amount, so that the required casting temperature (i.e., liquidus temperature) of the alloy can be reduced. The highest strengthening effect is obtained for compositions in which the sum of the dispersed (colloid) forming elements is at least equal to 2 wt.%. According to the Al-Cr and Al-V binary phase diagrams, 2 wt.% Cr will give the alloy a liquidus temperature of 780°C, while 1.7 wt.% V will give the alloy a liquidus temperature of about 950°C. By using a combination of 2% Cr and V, the liquidus temperature can be reduced, thereby reducing the required casting temperature.
[0183] By using three or more dispersed (colloid) forming elements, such as, for example, in alloys Nos. 14-17 and 19-20, the liquidus temperature can be further reduced. The liquidus temperature can be particularly reduced by reducing the amount of vanadium. The use of more different dispersed (colloid) forming elements appears to produce some synergistic effects on yield strength. This can be seen when comparing alloy No. 11 with alloy No. 10 and alloy No. 14 with alloy No. 13.
[0184] Alloy No. 11: Microstructure of Al-7Mg-2Mn-1V-1Cr
[0185] The microstructure of this alloy is Figures 5 to 8 The alloy was rapidly solidified and plastically consolidated by extrusion at 400°C. Transmission electron microscopy (TEM) micrographs show a large amount of dispersed (colloidal) particles, and the grain size is less than 1 μm. The dispersed (colloidal) particles are mainly located in the grain boundary region, but dispersed (colloidal) particles can also be seen in the grain boundary region at locations with high supersaturation of the alloy with chemical composition ( Figure 6 High magnification of the alloy microstructure shows that the size of the dispersed (colloidal) particles is in the range of less than 50 nm ( Figure 7 ). Both the high number and the small size of the dispersed (colloid) bodies contribute to the stabilization of the grains during the forming process. In TEM micrographs, small grain sizes cannot be clearly seen due to the low diffraction contrast between adjacent grains. In order to extract more detailed information about the grain size, the Transmission Kikuchi diffraction (TKD) method was used.
[0186] The TKD technique is characterized by the high spatial resolution required for submicron materials and provides correct statistical information about microstructural features. Figure 8The typical microstructure of the Al-7Mg-2Mn-1V-1C alloy obtained by TKD is shown in Figure 1. The average grain size calculated according to ASTM E2627-13 (2019) is 510 nm.
[0187] Examples showing low forming stress
[0188] The high strength of the alloy according to the invention at room temperature is combined with low flow stresses under hot forming conditions. Exemplary results for the RS alloy are provided in Table 2 and compared with the results for the most common medium strength EN-AW 6082T6 alloy (which has been precipitation hardened by a T6 temperature treatment) and the commercially pure aluminum EN-AW1050. The data are obtained from a deformation speed of 10 - 2 s -1 The flow stress is the maximum flow stress at a specified temperature when the alloy sample is compacted to 50% of its initial height.
[0189] Table 2: True yield strength (YS, R) of various alloys deformed at high temperature at room temperature 0.2 , in MPa) and flow stress at high temperature (FS, in MPa)
[0190]
[0191] Alloys with high strength at room temperature exhibit very low flow stresses under hot forming conditions. Depending on the deformation temperature, the flow stress ranges from 10 to 1.5 MPa. At 525°C, the flow stress is only about 1% or even less of the yield strength of the alloy at 20°C, while the flow stress of the most common EN-AW 6082T6 alloy is about 5% of its room temperature yield strength. In addition, the yield strength of this alloy is measured after precipitation hardening, while the flow stress is measured before precipitation hardening, i.e., when the alloy has a much lower yield strength (on the order of 110 MPa). Therefore, without T6 heat treatment, the flow stress is equal to about 15% of its yield strength.
[0192] It is known that solid solution strengthening also exists under high temperature forming conditions. The opposite effect for RS alloys with a higher concentration of dispersed (colloidal) body forming elements is the result of grain boundary sliding phenomena, which are active for submicron materials. In the above-mentioned article by T. Tokarski et al. (2012), the fine grain size of the alloy also reduces the flow strength. The flow stress at 450°C can be reduced from 48MPa to 19MPa, but the alloy strength is low, that is, the yield strength at room temperature is only 320MPa. In contrast, the high-strength aluminum alloy Al-7Mg-2Mn-1V-1Cr has a flow stress of only about 16MPa at 450°C and a yield strength of up to 624MPa. In addition, the high-strength aluminum alloy according to the present invention has higher thermal stability and can only lose a small part of its strength, so that it can be hot deformed at higher temperatures, and thus much lower hot forming stresses can be achieved.
[0193] Examples of Ductile High Strength Alloys
[0194] The alloy according to the present invention can not only have high strength at room temperature, but also have high elongation combined with still high strength. Table 3 shows the composition and mechanical properties of six rapid solidification and plastic solidification alloys according to the present invention, including two alloys with elongation higher than 15% (alloys No. 22 and No. 23) and four alloys with lower elongation but higher yield strength (alloys No. 24 to No. 27).
[0195] Table 3: Composition (wt.%), mechanical strength (YS, R) of rapidly solidified and ductile alloys and two solution and artificially aged (T6 treated) standard alloy compositions 0.2 : True yield strength, in MPa and UTS: Ultimate tensile strength (in MPa) and elongation at break (El, %).
[0196]
[0197]
[0198] Alloys No. 22 to No. 27 all have yield strengths that satisfy equation (1) and even equation (2), ie, the yield strength (MPa) is higher than 525 or 530 minus ten times the percent elongation at break.
[0199] Heat treated standard alloys EN-AW 082 and EN-AW 061 have similar yield strengths to alloys No. 22 and 23, but much lower elongations.
[0200] The alloys according to the invention therefore not only offer high to very high yield strengths, but can even offer a combination of high elongation and high yield strength, thereby offering new opportunities in applications such as automotive applications, where low weight has to be combined with high strength and high ductility.
[0201] Examples Demonstrating Improved Thermal Stability
[0202] One of the unique features of the alloy according to the invention is that it can withstand higher forming temperatures without significant loss of its mechanical properties. It allows the production of ready-to-use components in the hardened state. An example of the hardness of the alloy after the hot forming process is presented in Table 3. The hot forming process was simulated by a compression test, in which the alloy was plastically consolidated (extruded) at 400°C and deformed to 50% of its initial height. The thermal stability test was carried out in a temperature range of 450°C to 550°C and a deformation speed of 10 -2 s -1 Increasing the forming temperature to 50°C above the extrusion temperature results in a loss of about 5% of the initial hardness. As the temperature increases, the hardness loss is greater, however, in the most extreme case of 550°C (550°C is a temperature slightly below the solidus temperature of the tested alloy), the hardness loss does not exceed about 20%. Depending on the desired final strength of the hot formed component, a suitable temperature can be selected, taking into account that an increase in temperature will result in a reduction in force during the forming process.
[0203] Table 3: Vickers hardness of the alloy after hot forming process at different temperatures.
[0204] Al-7Mg-2Mn-1V-0.5Cr Al-7Mg-2Mn-0.5V-0.5Cr Extrusion at 400°C 190 186 Compression 450℃ 181 178 Compression 500℃ 170 164 Compression 525℃ 168 156 Compression 550℃ 150 143
Claims
1. A rapidly solidified and plastically consolidated aluminum alloy, wherein the aluminum alloy comprises aluminum (Al) and: - between 3.00 wt.% and 10.00 wt.% magnesium (Mg); - greater than 1.00 and less than 6.00 wt. % manganese (Mn); and - one or more transition elements, said transition elements being chosen from the group consisting of chromium (Cr), vanadium (V), titanium (Ti), zirconium (Zr), molybdenum (Mo), cobalt (Co) and niobium (Nb), said one or more transition elements having a total amount at least equal to 0.50 wt.%, and said maximum amount of transition elements being: 1.50 wt.% for Cr, 1.50 wt.% for V, 1.00 wt.% for Ti, 1.00 wt.% for Zr, 1.50 wt.% for Mo, 1.50 wt.% for Co and 1.00 wt.% for Nb. in, The aluminum alloy comprises: - contains no or less than 2.00 wt.%, preferably less than 1.00 wt.% of zinc (Zn); no or less than 2.00 wt.%, preferably less than 1.00 wt.% of silicon (Si); no or less than 1.00 wt.% of scandium (Sc); and no or less than 1.00 wt.% of tungsten (W); - does not contain other elements than Al, Mg, Mn, Cr, V, Ti, Zr, Mo, Co, Nb, Zn, Si, Sc and W, or the total amount of said other elements is less than 4.00 wt.%, preferably less than 2.0 wt.% and more preferably less than 1.00 wt.%; and - Aluminum as balance.
2. The aluminum alloy according to claim 1, comprising at most 1.20 wt.%, preferably at most 1.00 wt.%, and more preferably at most 0.75 wt.% V.
3. The aluminum alloy according to claim 1 or 2, comprising at most 1.40 wt.%, preferably at most 1.30 wt.% and more preferably at most 1.20 wt.% Cr.
4. The aluminum alloy according to any one of claims 1 to 3, comprising at least 0.10 wt.%, preferably at least 0.20 wt.%, more preferably at least 0.30 wt.% and most preferably at least 0.40 wt.% Cr.
5. The aluminum alloy according to any one of claims 1 to 4, comprising at least 0.10 wt.%, preferably at least 0.20 wt.%, more preferably at least 0.30 wt.%, and most preferably at least 0.40 wt.% V.
6. The aluminum alloy according to any one of claims 1 to 5, comprising two or more, preferably three or more, of the transition elements.
7. The aluminum alloy according to any one of claims 1 to 6, comprising Cr and V in a total amount of at least 0.50 wt.%, preferably at least 0.70 wt.%, and more preferably at least 0.90 wt.%.
8. The aluminum alloy according to any one of claims 1 to 7, comprising Cr and / or V, and additionally comprising: at least 0.15 wt.%, preferably at least 0.20 wt.% Ti; at least 0.15 wt.%, preferably at least 0.20 wt.% Zr; At least 0.15 wt.%, preferably at least 0.20 wt.% Mo; at least 0.15 wt.%, preferably at least 0.20 wt.% Co; and / or, at least 0.15 wt.%, preferably at least 0.20 wt.% Nb.
9. The aluminum alloy according to any one of claims 1 to 8, wherein The total amount of the one or more transition elements is greater than 0.70 wt.%, preferably greater than 0.80 wt.%, more preferably greater than 0.90 wt.% and most preferably greater than 1.00 wt.%.
10. The aluminum alloy according to any one of claims 1 to 9, wherein The total amount of the one or more transition elements is less than 3.00 wt.%, preferably less than 2.75 wt.%, more preferably less than 2.50 wt.% and most preferably less than 2.25 wt.%.
11. The aluminum alloy according to any one of claims 1 to 10, comprising at least 1.10 wt.%, preferably at least 1.20 wt.%, more preferably at least 1.30 wt.% and most preferably at least 1.40 wt.% Mn.
12. The aluminum alloy according to any one of claims 1 to 11, comprising less than 5.00 wt.%, preferably less than 4.50 wt.%, and more preferably less than 4.00 wt.% Mn.
13. The aluminum alloy according to any one of claims 1 to 12, comprising at least 4.00 wt.%, preferably at least 4.50 wt.%, more preferably at least 5.00 wt.%, most preferably at least 5.50 wt.% and even more preferably at least 6.00 wt.% Mg.
14. The aluminum alloy according to any one of claims 1 to 13, comprising less than 9.00 wt.%, preferably less than 8.00 wt.% and more preferably less than 7.00 wt.% Mg.
15. The aluminum alloy according to any one of claims 1 to 14, wherein the aluminum alloy has a true yield strength (YS, R) measured at 20°C according to ASTM E8 / E8M-13a. 0.2 ) is at least 400 MPa, preferably at least 450 MPa, more preferably at least 500 MPa and most preferably at least 550 MPa.
16. The aluminum alloy according to any one of claims 1 to 15, wherein the aluminum alloy is -2 The maximum true stress during plastic deformation in compression testing with a true strain rate of less than 25 MPa, preferably less than 21 MPa and more preferably less than 18 MPa at 450°C, and / or less than 20 MPa, preferably less than 17 MPa and more preferably less than 14 MPa at 500°C, and / or less than 17 MPa, preferably less than 14 MPa and more preferably less than 8 MPa at 550°C.
17. The aluminum alloy according to any one of claims 1 to 16, wherein the aluminum alloy has a true yield strength (YS, R) measured at 20°C according to ASTM E8 / E8M-13a. 0.2 ), and at a temperature of 525°C and a rate of 10 -2 The maximum true stress when plastically deformed to 50% of the initial height in a compression test at a true strain rate of , the maximum true stress expressed in MPa is less than 3.0% of the true yield strength expressed in MPa, preferably less than 2.0% and more preferably less than 1.5%.
18. The aluminum alloy according to claim 1, comprising between 1.50 wt.% and 3.50 wt.%, preferably between 2.00 wt.% and 3.00 wt.%, Mn, and between 3.00 wt.% and 5.00 wt.%, preferably between 3.00 wt.% and 4.50 wt.%, Mg, the total amount of the one or more transition elements being less than 1.00 wt.%, and Cr being preferably absent or present in an amount of at most 0.3 wt.%, or preferably at most 0.2 wt.%.
19. The aluminum alloy according to claim 18, wherein the aluminum alloy has a percent elongation at break (el) of at least 15%, preferably at least 18%, and a true yield strength (YS, R 0.2 ) is at least 320 MPa, preferably at least 340 MPa, the elongation at break percentage and the true yield strength are measured according to ASTM E8 / E8M-13a at 20°C, and the true yield strength is preferably further defined by the following equation: YS>525-10.el (Equation 1) 20. The aluminum alloy according to any one of claims 1 to 19, wherein the aluminum alloy does not contain or includes less than 3.00wt.% Fe, preferably does not contain or includes less than 2.00wt.% Fe and more preferably does not contain or includes less than 1.00wt.% Fe, and does not contain or includes less than 2.00wt.% Cu, does not contain or includes less than 1.00wt.% Cu, and does not contain or includes less than 0.40wt.% Ni, preferably does not contain or includes less than 0.30wt.% Ni, and does not contain or includes less than 0.40wt.% Bi, preferably does not contain or includes less than 0.30wt.% Bi, and does not contain or includes less than 0.40wt.% Sn, preferably does not contain or includes less than 0.30wt.% Sn, and does not contain or includes less than 0.40wt.% Pb, preferably does not contain or includes less than 0.30wt.% Pb.
21. The aluminum alloy according to any one of claims 1 to 20, having a liquidus temperature below 950°C, preferably below 900°C and more preferably below 850°C.
22. The aluminum alloy according to any one of claims 1 to 21, having an average grain size at the time of plastic consolidation measured according to standard ASTM E2627-13 (2019) of less than 2000 nm, preferably less than 1000 nm, more preferably less than 800 nm and most preferably less than 600 nm.
23. The aluminum alloy according to any one of claims 1 to 22, wherein the aluminum alloy is hot forged, in particular die forged, and the average grain size of the aluminum alloy measured according to standard ASTM E2627-13 (2019) is less than 4000nm, preferably less than 2000nm, more preferably less than 1500nm and most preferably less than 1200nm.
24. The aluminum alloy of any one of claims 1 to 23, being substantially free of primary intermetallic phases, and preferably also free of dendrites.
25. A method for producing an aluminum alloy according to any one of claims 1 to 24, the aluminum alloy having liquidus and solidus temperatures, and a predetermined difference between the liquidus temperature and the solidus temperature, in which method a molten aluminum alloy composition having a composition as defined in any one of claims 1 to 24 is prepared, wherein: The molten aluminum alloy composition is rapidly solidified in the form of a rapidly solidifying sheet of material, and wherein the rapidly solidifying sheet of material is plastically consolidated to produce a plastically consolidated aluminum alloy.
26. The method according to claim 25, wherein: The liquidus temperature is below 950°C, preferably below 900°C and more preferably below 850°C.
27. The method according to claim 25 or 26, wherein: The molten aluminum alloy composition is ejected from at least one nozzle to rapidly solidify, the molten aluminum alloy composition exiting the at least one nozzle having a predetermined temperature when exiting the at least one nozzle, and rapidly solidified by cooling to the solidus temperature of the aluminum alloy at an average cooling rate within a predetermined time period, the average cooling rate being determined as the ratio of the difference between the predetermined temperature and the solidus temperature across the predetermined time period, and the average cooling rate being higher than 10,000°C / sec.
28. The method according to claim 27, wherein: The predetermined temperature is higher than the solidus temperature by at least 75% of the liquidus / solidus temperature difference, the predetermined temperature is preferably equal to or higher than the liquidus temperature, and more preferably at least 10°C higher than the liquidus temperature.
29. The method according to claim 27 or 28, wherein: The molten aluminum alloy composition is supplied to the at least one nozzle through a conduit and is additionally heated in the conduit before being ejected from the nozzle, the conduit preferably being substantially completely filled with the aluminum alloy composition.
30. The method according to any one of claims 25 to 29, wherein: The rapidly solidifying material sheet is plastically consolidated by plastic deformation under pressure at a temperature of at least 300°C, preferably at least 400°C and more preferably at least 450°C.
31. The method according to any one of claims 25 to 30, wherein: The rapidly solidifying material sheet is plastically consolidated at a temperature below the solidus temperature of the alloy, preferably at least 10°C below the solidus temperature, but above 350°C, preferably above 375°C and more preferably above 400°C, most preferably between 400°C and 550°C.
32. The method according to any one of claims 25 to 31, wherein: The rapidly solidified material sheet is consolidated by plastic deformation to reduce the average grain size of the consolidated aluminum alloy measured according to standard ASTM E2627-13 (2019) to a value less than 2000nm, preferably less than 1000nm, more preferably less than 800nm and most preferably less than 600nm.
33. A method according to any one of claims 25 to 32, wherein: Consolidation is carried out by extruding the sheet of rapidly solidifying material with a cross-sectional reduction λ of at least 3, preferably at least 6, more preferably at least 8 and most preferably at least 10.
34. A method according to any one of claims 25 to 33, wherein: The consolidated aluminum alloy is hot forged, in particular die forged.
35. The method of claim 34, wherein: The consolidated aluminium alloy is hot forged at a temperature above 400°C, preferably above 450°C and more preferably above 475°C or above 500°C, but below the solidus temperature of the alloy, preferably at least 10°C below the solidus temperature.
